Method for producing pressure-sensitive adhesive layer-attached polarizing plate

By adding antistatic agent to the adhesive layer of the polarizing plate and setting a rounded corner design, combined with specific resistivity change conditions, the problem of easy peeling of the adhesive layer of the polarizing plate under physical impact is solved, and the high impact resistance and good adhesion of the polarizing plate are achieved.

JP7628396B2Active Publication Date: 2025-02-10SUMITOMO CHEM CO LTD
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
JP2020076867
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-07-17
Filing Date
2020-04-23
Publication Date
2025-02-10
Estimated Expiration
2040-04-23

AI Technical Summary

Technical Problem

In the prior art, polarizers containing an adhesive layer containing an antistatic agent are easily peeled off when subjected to physical impact, and are easily transmitted by design, resulting in a decrease in adhesive strength.

Method used

A polarizer is designed, the adhesive layer contains antistatic agent, and a rounded corner with a radius of 1.0 mm or more is provided at four corners, and the resistivity change rate ΔR after being maintained at 85°C for 100 hours meets specific conditions to ensure the tight bond between the adhesive layer and the display element.

Benefits of technology

Even under physical impact, the polarizing plate is difficult to peel off, maintaining good bonding strength and preventing peeling of the adhesive layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007628396000006
    Figure 0007628396000006
  • Figure 0007628396000007
    Figure 0007628396000007
  • Figure 0007628396000008
    Figure 0007628396000008
Patent Text Reader

Abstract

To provide a polarizer with an adhesive layer including an anti-static agent and prevented from peeling even when receiving a physical impulse.SOLUTION: A polarizer 25 with an adhesive layer, including a polarizer 10 and an adhesive layer 20 laminated in contact with the polarizer 10 has four sides and four corners in which at least one has a curvature radius of 1.0 mm or more and is round. The adhesive layer 20 includes an anti-static agent; when setting the respective values of resistance of the surface of the adhesive layer 20 on the side opposite to the polarizer 10 side before and after being held at a temperature of 85°C for 100 hours to R1 [Ω / square] and R2 [Ω / square], the rate ΔR [%] of change calculated by the formula (3) satisfies the relationship of the formula (1):ΔR=[(R2-R1) / R1]×100 (3), ΔR≥25 (1).SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a pressure-sensitive adhesive layer-attached polarizing plate including a polarizing plate and a pressure-sensitive adhesive layer, and an image display device. [Background technology]

[0002] Polarizing plates, which are formed by laminating a protective film on one or both sides of a polarizer, are optical components that are widely used in image display devices such as liquid crystal displays (e.g., mobile televisions) and organic electroluminescence (OLED) displays, and in recent years in various mobile devices such as mobile phones, smartphones, and tablet terminals. Polarizing plates are often used by being attached to image display elements (such as liquid crystal cells and organic EL display elements) via an adhesive layer (see, for example, JP 2010-229321 A (Patent Document 1)). For this reason, polarizing plates are sometimes distributed on the market in the form of adhesive layer-attached polarizing plates in which an adhesive layer is previously provided on one surface of the polarizing plate. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2010-229321 A Summary of the Invention [Problem to be solved by the invention]

[0004] The pressure-sensitive adhesive layer-attached polarizing plate can improve the antistatic performance by being configured to include a pressure-sensitive adhesive layer containing an antistatic agent. However, when the pressure-sensitive adhesive layer contains an antistatic agent, the adhesion strength is reduced, so that peeling is likely to occur due to physical impact, and in a form in which the polarizing plate is attached close to the edge of the panel from the viewpoint of design, the physical impact is likely to be transmitted to the pressure-sensitive adhesive layer, and the peeling problem becomes more prominent.

[0005] The present invention aims to provide a polarizing plate having an adhesive layer containing an antistatic agent, which is unlikely to peel off even when subjected to physical impact, and also aims to provide an image display device including such an adhesive layer-attached polarizing plate. [Means for solving the problem]

[0006] The present invention provides a pressure-sensitive adhesive layer-attached polarizing plate and an image display device as described below. [1] A pressure-sensitive adhesive layer-attached polarizing plate comprising a polarizing plate and a pressure-sensitive adhesive layer laminated in contact with the polarizing plate, It has four sides and four angles, At least one of the four corners is a round corner having a curvature radius of 1.0 mm or more; The pressure-sensitive adhesive layer contains an antistatic agent, A polarizing plate with an adhesive layer, in which the resistance values ​​of the surface of the adhesive layer opposite the polarizing plate before and after being held at a temperature of 85°C for 100 hours are R1 [Ω / □] and R2 [Ω / □], respectively, and the rate of change ΔR [%] calculated by equation (3) satisfies the relationship of equation (1). ΔR = [(R2-R1) / R1] × 100 (3) ΔR≧25 (1) [2] The pressure-sensitive adhesive layer-attached polarizing plate according to [1], which has a rectangular outer shape. [3] The polarizing plate includes a polarizer layer and a first protective film, the first protective film is a polar resin film, The pressure-sensitive adhesive layer-attached polarizing plate according to [1] or [2], wherein the first protective film and the pressure-sensitive adhesive layer are in contact with each other. [4] The polarizing plate includes a polarizer layer and a cured layer of a curable resin composition, The pressure-sensitive adhesive layer-attached polarizing plate according to [1] or [2], wherein the cured layer of the curable resin composition and the pressure-sensitive adhesive layer are in contact with each other. [5] An image display device comprising: an image display element; and the pressure-sensitive adhesive layer-attached polarizing plate according to any one of [1] to [4], wherein the pressure-sensitive adhesive layer is laminated in contact with the image display element. [6] The outer shape of the pressure-sensitive adhesive layer-attached polarizing plate is located within the outer shape of the image display element, The image display device according to [5], wherein the pressure-sensitive adhesive layer-attached polarizing plate has an outer shape in which the outer shape portion is 1.0 mm or less away from the outer shape of the image display element is longer than the outer shape portion in which the outer shape portion is more than 1.0 mm away. [7] An image display device comprising: an image display element; and the pressure-sensitive adhesive layer-attached polarizing plate according to [1] or [2], wherein the pressure-sensitive adhesive layer is laminated in contact with the image display element. [8] The outer shape of the pressure-sensitive adhesive layer-attached polarizing plate is located within the outer shape of the image display element, The image display device according to [7], wherein the distance between the rounded corners of the outer shape of the pressure-sensitive adhesive layer-attached polarizing plate and the outer shape of the image display element is 1.0 mm or less. Effect of the Invention

[0007] According to the present invention, it is possible to provide a pressure-sensitive adhesive layer-attached polarizing plate that is not easily peeled off even when subjected to a physical impact. [Brief description of the drawings]

[0008] [Figure 1] 1 is a schematic cross-sectional view showing an example of a pressure-sensitive adhesive layer-attached polarizing plate and an image display device according to the present invention. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing another example of a pressure-sensitive adhesive layer-attached polarizing plate and an image display device according to the present invention. [Diagram 3] FIG. 2 is a schematic cross-sectional view showing still another example of the pressure-sensitive adhesive layer-attached polarizing plate and image display device according to the present invention. [Figure 4] FIG. 2 is a top view showing an example of the external shape of a pressure-sensitive adhesive layer-attached polarizing plate according to the present invention. [Diagram 5] FIG. 1 shows an example of the relationship between the contour of an adhesive layer-attached polarizing plate in an image display device and the contour of an image display element, where (a) is a top view showing the relationship when the corners are rounded, and (b) is a top view showing the relationship when the corners are right angles. [Figure 6] FIG. 2 is a top view showing an example of the outer shape of a right-angled rectangular pressure-sensitive adhesive layer-attached polarizing plate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] <Polarizing plate with adhesive layer> [1] Structure of polarizing plate with adhesive layer The adhesive layer-attached polarizing plate includes a polarizing plate and an adhesive layer laminated in contact with the polarizing plate. The adhesive layer includes an antistatic agent. When the resistance values ​​of the surface of the adhesive layer opposite to the polarizing plate side before and after holding at a temperature of 85°C for 100 hours are R1 [Ω / □] and R2 [Ω / □], respectively, the rate of change ΔR [%] calculated by formula (3) satisfies the relationship of formula (1) and may also satisfies the relationship of formula (1'). ΔR = [(R2-R1) / R1] × 100 (3) ΔR≧25 (1) ΔR≧50 (1') The relationship may be satisfied.

[0010] 1 to 3 show examples of the layer structure of the adhesive layer-attached polarizing plate. The adhesive layer-attached polarizing plate 25 shown in FIG. 1 includes a polarizing plate 10 and an adhesive layer 20 laminated in contact with the polarizing plate 10. The polarizing plate 10 has a polarizer 1, a first protective film 4 attached to the surface of the polarizer 1 on the adhesive layer 20 side, and a second protective film 3 attached to the surface of the polarizer 1 opposite to the adhesive layer 20 side. As in the example shown in FIG. 1, the second protective film 3 can have a surface treatment layer 2 formed on its outer surface (the surface opposite to the polarizer 1). The adhesive layer 20 is laminated in contact with the first protective film 4. The first protective film 4 is preferably a polar resin film. When the first protective film 4 in contact with the adhesive layer 20 is a polar resin film, it is possible to easily configure an adhesive layer-attached polarizing plate that satisfies the relationship of formula (1). The adhesive layer 20 can be used for bonding to, for example, an image display element 30.

[0011] The pressure-sensitive adhesive layer-attached polarizing plate 26 shown in Fig. 2 is the same as that shown in Fig. 1, except that it has a curable resin composition cured layer 5 instead of the first protective film 4 of the pressure-sensitive adhesive layer-attached polarizing plate 25 shown in Fig. 1. The pressure-sensitive adhesive layer 20 is laminated in contact with the curable resin composition cured layer 5. By having the curable resin composition cured layer 5 in contact with the pressure-sensitive adhesive layer 20, it is possible to easily configure a pressure-sensitive adhesive layer-attached polarizing plate that satisfies the relationship of formula (1).

[0012] The pressure-sensitive adhesive layer-attached polarizing plate 27 shown in Fig. 3 is the same as that shown in Fig. 1, except that it has a curable resin composition cured layer 5 formed on the outer surface (the surface opposite to the polarizer 1) of the first protective film 4 of the pressure-sensitive adhesive layer-attached polarizing plate 25 shown in Fig. 1. The pressure-sensitive adhesive layer 20 is laminated in contact with the curable resin composition cured layer 5. By having the curable resin composition cured layer 5 in contact with the pressure-sensitive adhesive layer 20, it is possible to easily configure a pressure-sensitive adhesive layer-attached polarizing plate that satisfies the relationship of formula (1).

[0013] The pressure-sensitive adhesive layer-attached polarizing plates 25 , 26 , and 27 may have a separate film on the outer surface of the pressure-sensitive adhesive layer 20 to protect the exposed surface of the pressure-sensitive adhesive layer 20 and be laminated releasably from the pressure-sensitive adhesive layer.

[0014] The adhesive layer-attached polarizing plates 25, 26, and 27 are preferably rectangular or substantially rectangular polarizing plate sheets. In the case of sheets, the size is preferably 100 mm×40 mm or more, more preferably 150 mm×40 mm or more. The size of the sheets is, for example, 1650 mm×930 mm or less, preferably 1430 mm×810 mm or less.

[0015] FIG. 4 shows an example of a preferred outer shape of the adhesive layer-attached polarizing plate 25, 26, 27. The outer shape 28 of the adhesive layer-attached polarizing plate shown in FIG. 4 has four sides 28a, 28b, 28c, 28d and four corners. This adhesive layer-attached polarizing plate has a rectangular outer shape. The four sides are two short sides 28a, 28c and two long sides 28b, 28d. The four corners refer to part C formed by the connection parts of two adjacent sides, and all corners are round in the outer shape 28 of the adhesive layer-attached polarizing plate. An outer shape with four round corners has excellent design. In the outer shape 28 of the adhesive layer-attached polarizing plate, the side parts other than part C formed by the connection parts of the two sides are part A. The outer shape of the adhesive layer-attached polarizing plate is not limited to the shape shown in FIG. 4, but it is preferable that the adhesive layer-attached polarizing plate has four corners, and at least one corner is round with a radius of curvature of 1.0 mm or more.

[0016] FIG. 5(a) shows an example of the relationship between the outer shape 28 of the adhesive layer-attached polarizing plate and the outer shape 31 of the image display element 30 in an image display device. In FIG. 5(a), the outer shape 28 of the adhesive layer-attached polarizing plate is one size smaller than the outer shape 31 of the image display element from the viewpoint of easy attachment, and is located within the outer shape 31 of the image display element. In addition, the distance d between the outer shape 28 of the adhesive layer-attached polarizing plate and the outer shape 31 of the image display element is preferably 1.0 mm or less in terms of excellent appearance. It is preferable that the distance d is 1.0 mm or less over the entire circumference of the outer shape 28 of the adhesive layer-attached polarizing plate, and it is also preferable that the variation in the distance d is small over the entire circumference of the outer shape 28 of the adhesive layer-attached polarizing plate, and the difference between the maximum value and the minimum value is within 0.2 mm, but is not limited thereto. It is preferable that the distance d of the outer shape part where the distance d is 1.0 mm or less is longer than the outer shape part where the distance d is more than 1.0 mm. 5(a), when part C in outer shape 28 of the adhesive layer-attached polarizing plate has rounded corners and all four corners of outer shape 31 of the image display element are also rounded, the distance dc of part C can be configured to be the same as the distance d of the other part, part A, which is preferable because it is possible to reduce the variation in distance d over the entire circumference of outer shape 28 of the adhesive layer-attached polarizing plate. From the viewpoint of improving design, the distance dc of part C is also preferably 1.0 mm or less.

[0017] Fig. 5(b) shows a different relationship between the outer shapes of the pressure-sensitive adhesive layer-attached polarizing plate and the image display element in that the corners of the outer shapes are right angles. As shown in Fig. 5(b), when all parts C in the outer shape 28b of the pressure-sensitive adhesive layer-attached polarizing plate are right angles and all corners of the outer shape 31b of the image display element are also right angles, the distance dc of the corners of part C is usually about √2×d, where d is the distance of part A.

[0018] Portable image display devices such as smartphones are often subjected to physical shocks due to being dropped or the like. The four corners of an image display device are more susceptible to physical shocks than other parts because they protrude. As shown in FIG. 5(a), in an embodiment in which the corners are rounded and the distance dc between the corners and the outer shape 31 of the image display element is as short as other parts, the physical shock received at the corners is transmitted to the adhesive layer without being attenuated, which makes it easy to cause peeling. On the other hand, as shown in FIG. 5(b), in an embodiment in which the four corners are right angles and the distance dc between the corners and the outer shape 31b of the image display element is longer than other parts, the physical shock received at the corners is easily attenuated, which makes it easy to suppress peeling. When the adhesive layer 20 contains an antistatic agent, the adhesive strength between the adhesive layer 20 and the polarizing plate is low, so the peeling problem becomes more pronounced. According to the present invention, even when the outer shape of the adhesive layer-attached polarizing plate has rounded corners, it has excellent impact resistance.

[0019] The pressure-sensitive adhesive layer-attached polarizing plate of the present invention can suppress peeling due to physical impact, even when the pressure-sensitive adhesive layer 20 contains an antistatic agent, by the pressure-sensitive adhesive layer 20 satisfying the relationship of formula (1). When the resistance values ​​of the pressure-sensitive adhesive layer on the surface opposite to the polarizing plate side before and after holding at a temperature of 85° C. for 100 hours are R1 [Ω / □] and R2 [Ω / □], respectively, it is preferable that the rate of change ΔR [%] calculated by formula (3) satisfies the relationship of formula (2). ΔR = [(R2-R1) / R1] × 100 (3) ΔR≦98 (2)

[0020] It is believed that the reason why peeling is less likely to occur even when subjected to physical impact when ΔR satisfies formula (1) is as follows. The adhesive layer adheres to the image display element due to the adhesive force exerted by the adhesive exposed on the surface. If the adhesive layer contains an antistatic agent and a large amount of this antistatic agent is present on the surface, the amount of antistatic agent exposed on the surface will be relatively large, and the proportion of the adhesive will be relatively small. Since the antistatic agent does not contribute to adhesion, the adhesive force with the image display element will decrease, making the polarizing plate more likely to peel off due to physical impact.

[0021] On the other hand, formula (1) indicates that the antistatic agent is likely to move from the surface of the adhesive layer. That is, ΔR of 25 or more (formula (1)) indicates that the antistatic agent is likely to move toward the inside of the adhesive layer, that is, the amount of antistatic agent exposed on the surface is likely to decrease. When the amount of antistatic agent exposed on the surface decreases, the amount of exposed adhesive increases relatively, resulting in a stronger adhesion to the image display element.

[0022] More specifically, ΔR can be considered to be a value that indirectly indicates the proportion of antistatic agent that has migrated toward the inside of the adhesive layer, among the antistatic agent present on the surface of the adhesive layer, by maintaining the adhesive layer at a temperature of 85°C for 100 hours.

[0023] [2] Polarizing plate Polarizing plate 10 constituting pressure-sensitive adhesive layer-attached polarizing plates 25, 26, 27 includes at least polarizer 1, and typically includes polarizer 1 and a thermoplastic resin film as a protective film or the like laminated and attached to at least one surface of the polarizer.

[0024] [2-1] Polarizer Polarizer 1 is a film that has the function of selectively transmitting linearly polarized light in one direction from natural light. Examples include iodine-based polarizers in which iodine as a dichroic pigment is adsorbed and oriented on a polyvinyl alcohol-based resin film, dye-based polarizers in which a dichroic dye as a dichroic pigment is adsorbed and oriented on a polyvinyl alcohol-based resin film, and coated polarizers in which a dichroic dye in a lyotropic liquid crystal state is coated, oriented, and fixed. These polarizers are called absorptive polarizers because they selectively transmit linearly polarized light in one direction from natural light and absorb linearly polarized light in the other direction.

[0025] The polarizer 1 is not limited to an absorptive polarizer, and may be a reflective polarizer that selectively transmits linearly polarized light in one direction from natural light and reflects linearly polarized light in the other direction, or a scattering polarizer that scatters linearly polarized light in the other direction, but an absorptive polarizer is preferred from the viewpoint of excellent visibility. Among them, a polyvinyl alcohol polarizer made of a polyvinyl alcohol resin is more preferred, a polyvinyl alcohol polarizer in which a dichroic pigment such as iodine or a dichroic dye is adsorbed and oriented in a polyvinyl alcohol resin film is even more preferred, and a polyvinyl alcohol polarizer in which iodine is adsorbed and oriented in a polyvinyl alcohol resin film is particularly preferred.

[0026] As the polyvinyl alcohol resin constituting the polyvinyl alcohol polarizer, a saponified polyvinyl acetate resin can be used. Examples of the polyvinyl acetate resin include polyvinyl acetate, which is a homopolymer of vinyl acetate, and copolymers of vinyl acetate with other monomers copolymerizable therewith. Examples of other monomers copolymerizable with vinyl acetate include unsaturated carboxylic acids, olefins, vinyl ethers, unsaturated sulfonic acids, and (meth)acrylamides having an ammonium group.

[0027] The saponification degree of the polyvinyl alcohol resin is usually 85 mol% or more and 100 mol% or less, and preferably 98 mol% or more. The polyvinyl alcohol resin may be modified, and for example, polyvinyl formal or polyvinyl acetal modified with aldehydes can be used. The average polymerization degree of the polyvinyl alcohol resin is usually 1000 or more and 10000 or less, and preferably 1500 or more and 5000 or less. The average polymerization degree of the polyvinyl alcohol resin can be determined in accordance with JIS K 6726.

[0028] Such a polyvinyl alcohol-based resin is formed into a film and used as the raw film of the polarizer 1. The method for forming the polyvinyl alcohol-based resin into a film is not particularly limited, and a known method is adopted. The thickness of the polyvinyl alcohol-based raw film is, for example, 150 μm or less, preferably 100 μm or less (for example, 50 μm or less), and 5 μm or more.

[0029] Polarizer 1 can be produced by a method including the steps of uniaxially stretching a polyvinyl alcohol-based resin film; dyeing the polyvinyl alcohol-based resin film with a dichroic dye to adsorb the dichroic dye; treating the polyvinyl alcohol-based resin film with the adsorbed dichroic dye with an aqueous boric acid solution (crosslinking treatment); and washing with water after the treatment with the aqueous boric acid solution.

[0030] The uniaxial stretching of the polyvinyl alcohol-based resin film can be performed before, simultaneously with, or after dyeing with a dichroic dye. When the uniaxial stretching is performed after dyeing, the uniaxial stretching may be performed before or during the boric acid treatment. The uniaxial stretching may also be performed in a plurality of these stages.

[0031] In the uniaxial stretching, the film may be stretched uniaxially between rolls having different peripheral speeds, or may be stretched uniaxially using a heated roll. The uniaxial stretching may be dry stretching in which stretching is performed in the atmosphere, or wet stretching in which stretching is performed in a state where the polyvinyl alcohol-based resin film is swollen using a solvent such as water. The stretching ratio is usually 3 times or more and 8 times or less.

[0032] A method for dyeing a polyvinyl alcohol-based resin film with a dichroic dye includes, for example, immersing the film in an aqueous solution containing the dichroic dye. As the dichroic dye, iodine or a dichroic organic dye is used. It is preferable that the polyvinyl alcohol-based resin film is immersed in water before the dyeing process.

[0033] The dyeing method using iodine includes a method of immersing a polyvinyl alcohol-based resin film in an aqueous solution containing iodine and potassium iodide. The content of iodine in this aqueous solution can be 0.01 parts by mass or more and 1 part by mass or less per 100 parts by mass of water. The content of potassium iodide can be 0.5 parts by mass or more and 20 parts by mass or less per 100 parts by mass of water. The temperature of this aqueous solution can be 20°C or more and 40°C or less. On the other hand, as a dyeing method using a dichroic organic dye, a method of immersing a polyvinyl alcohol resin film in an aqueous solution containing a dichroic organic dye can be mentioned. The aqueous solution containing the dichroic organic dye may contain an inorganic salt such as sodium sulfate as a dyeing assistant. The content of the dichroic organic dye in this aqueous solution is 1×10 per 100 parts by mass of water. -4 The amount of the aqueous solution may be from 20°C to 80°C.

[0034] The boric acid treatment method after dyeing with a dichroic dye includes a method of immersing the dyed polyvinyl alcohol resin film in a boric acid-containing aqueous solution. When iodine is used as the dichroic dye, the boric acid-containing aqueous solution preferably contains potassium iodide. The amount of boric acid in the boric acid-containing aqueous solution can be 2 parts by mass or more and 15 parts by mass or less per 100 parts by mass of water. The amount of potassium iodide in the aqueous solution can be 0.1 parts by mass or more and 20 parts by mass or less per 100 parts by mass of water. The temperature of the aqueous solution can be 50°C or more, for example, 50°C or more and 85°C or less.

[0035] The polyvinyl alcohol-based resin film after the boric acid treatment is usually washed with water. The washing can be performed, for example, by immersing the polyvinyl alcohol-based resin film after the boric acid treatment in water. The temperature of the water in the washing is usually 5° C. or more and 40° C. or less. After washing with water, a drying process is performed to obtain the polarizer 1. The drying treatment can be performed using a hot air dryer or a far infrared heater. A thermoplastic resin film as a protective film or the like can be attached to one or both sides of the polarizer 1 using an adhesive to obtain a polarizing plate 10.

[0036] Other examples of the manufacturing method of the polarizer 1 include the methods described in JP-A-2000-338329 and JP-A-2012-159778. In this method, a solution containing a polyvinyl alcohol resin is applied to the surface of a substrate film to provide a resin layer, and then a laminate film consisting of the substrate film and the resin layer is stretched, and then dyed, crosslinked, and the like to form a polarizer layer (polarizer) from the resin layer. This polarizing laminate film consisting of the substrate film and the polarizer layer can be obtained by laminating a thermoplastic resin film as a protective film or the like to the polarizer layer surface, and then peeling and removing the substrate film to form a polarizing plate 10 having a thermoplastic resin film on one side of the polarizer. If a thermoplastic resin film is further laminated to the polarizer layer surface exposed by peeling off the substrate film, a polarizing plate 10 having a thermoplastic resin film on both sides of the polarizer can be obtained.

[0037] The thickness of the polarizer 1 can be 40 μm or less, preferably 30 μm or less. According to the method described in JP-A-2000-338329 and JP-A-2012-159778, the thin film polarizer 1 can be more easily manufactured, and the thickness of the polarizer 1 can be more easily set to, for example, 20 μm or less, further 15 μm or less, further 10 μm or less or 8 μm or less. The thickness of the polarizer 1 is usually 2 μm or more, preferably 5 μm or more, and more preferably 10 μm or more. The thickness of the polarizer 1 may be 20 μm or more. Reducing the thickness of the polarizer 1 is advantageous for reducing the thickness of the polarizing plate 10, and further the pressure-sensitive adhesive layer-attached polarizing plate 25, laminated optical member, and image display device. On the other hand, increasing the thickness of the polarizer 1 increases the polarization degree of the polarizing plate 10 and is also advantageous in terms of durability of the polarizer 1. For this reason, the thickness of the polarizer 1 is appropriately selected according to the application.

[0038] [2-2] First protective film and second protective film The first protective film 4 and the second protective film 3 are attached to the surface of the polarizer 1. The first protective film 4 and the second protective film 3 are preferably thermoplastic resin films. The thermoplastic resin film may be a film made of a light-transmitting (preferably optically transparent) thermoplastic resin, for example, a polyolefin resin such as a chain polyolefin resin (such as a polypropylene resin) or a cyclic polyolefin resin (such as a norbornene resin); a cellulose ester resin such as triacetyl cellulose or diacetyl cellulose; a polyester resin such as polyethylene terephthalate, polyethylene naphthalate, or polybutylene terephthalate; a polycarbonate resin; a (meth)acrylic resin; or a mixture or copolymer thereof.

[0039] The thermoplastic resin film may be either an unstretched film or a uniaxially or biaxially stretched film. The biaxial stretching may be simultaneous biaxial stretching in which the film is stretched simultaneously in two stretching directions, or sequential biaxial stretching in which the film is stretched in a first direction and then stretched in a second direction different from the first direction. The thermoplastic resin film may be a protective film that plays a role in protecting the polarizer 1, or may be a protective film that also has an optical function such as a retardation film. A retardation film is an optically functional film used for the purpose of compensating for the retardation caused by a liquid crystal cell, which is an image display element, etc. For example, a retardation film having an arbitrary retardation value can be obtained by stretching (uniaxially stretching or biaxially stretching, etc.) a film made of the above-mentioned thermoplastic resin, or by forming a liquid crystal layer or the like on the thermoplastic resin film.

[0040] Examples of the linear polyolefin resin include homopolymers of linear olefins such as polyethylene resins and polypropylene resins, as well as copolymers of two or more types of linear olefins.

[0041] Cyclic polyolefin resin is a general term for resins containing cyclic olefins, such as norbornene, tetracyclododecene (also known as dimethanooctahydronaphthalene), or their derivatives, as polymerization units. Examples of cyclic polyolefin resins include ring-opening (co)polymers of cyclic olefins and their hydrogenated products, addition polymers of cyclic olefins, copolymers of cyclic olefins with linear olefins such as ethylene and propylene or aromatic compounds having vinyl groups, and modified (co)polymers of these modified with unsaturated carboxylic acids or their derivatives. Among these, norbornene-based resins using norbornene-based monomers such as norbornene and polycyclic norbornene-based monomers as the cyclic olefin are preferably used.

[0042] The cellulose ester resin is a resin in which at least a part of the hydroxyl groups in cellulose is esterified with acetate, and may be a mixed ester in which a part is esterified with acetate and a part is esterified with another acid. The cellulose ester resin is preferably an acetyl cellulose resin. Examples of the acetyl cellulose resin include triacetyl cellulose, diacetyl cellulose, cellulose acetate propionate, and cellulose acetate butyrate.

[0043] The polyester resin is a resin having an ester bond other than the above-mentioned cellulose ester resin, and is generally a polycondensate of a polyvalent carboxylic acid or a derivative thereof with a polyhydric alcohol. Examples of polyester resins include polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polytrimethylene terephthalate, polytrimethylene naphthalate, polycyclohexane dimethyl terephthalate, and polycyclohexane dimethyl naphthalate.

[0044] Examples of other copolymerization components include a dicarboxylic acid component and a diol component. Examples of the dicarboxylic acid component include isophthalic acid, 4,4'-dicarboxydiphenyl, 4,4'-dicarboxybenzophenone, bis(4-carboxyphenyl)ethane, adipic acid, sebacic acid, 5-sodium sulfoisophthalic acid, and 1,4-dicarboxycyclohexane. Examples of the diol component include propylene glycol, butanediol, neopentyl glycol, diethylene glycol, cyclohexanediol, an ethylene oxide adduct of bisphenol A, polyethylene glycol, polypropylene glycol, and polytetramethylene glycol. The dicarboxylic acid component and the diol component may each be used in combination of two or more kinds, if necessary. It is also possible to use a hydroxycarboxylic acid such as p-hydroxybenzoic acid, p-hydroxyethoxybenzoic acid, or β-hydroxyethoxybenzoic acid in combination with the above dicarboxylic acid component or diol component. As other copolymerization components, a small amount of a dicarboxylic acid component and / or a diol component having an amide bond, a urethane bond, an ether bond, a carbonate bond, etc. may be used.

[0045] Polycarbonate resins are polyesters formed from carbonic acid and glycol or bisphenol. Among them, aromatic polycarbonates having diphenylalkane in the molecular chain are preferably used from the viewpoints of heat resistance, weather resistance, and acid resistance. Examples of polycarbonates include polycarbonates derived from bisphenols such as 2,2-bis(4-hydroxyphenyl)propane (also known as bisphenol A), 2,2-bis(4-hydroxyphenyl)butane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 1,1-bis(4-hydroxyphenyl)isobutane, and 1,1-bis(4-hydroxyphenyl)ethane.

[0046] The (meth)acrylic resin may be, for example, a polymer containing a methacrylic acid ester as the main monomer (containing 50% by mass or more), and is preferably a copolymer in which a methacrylic acid ester is copolymerized with another copolymerization component. In one preferred embodiment, the (meth)acrylic resin contains methyl methacrylate or methyl methacrylate and methyl acrylate as copolymerization components.

[0047] Examples of copolymerization components other than methyl acrylate include methacrylic acid esters other than methyl methacrylate, such as ethyl methacrylate, n-, i- or t-butyl methacrylate, cyclohexyl methacrylate, phenyl methacrylate, benzyl methacrylate, 2-ethylhexyl methacrylate, and 2-hydroxyethyl methacrylate; acrylic esters such as ethyl acrylate, n-, i- or t-butyl acrylate, cyclohexyl acrylate, phenyl acrylate, benzyl acrylate, 2-ethylhexyl acrylate, and 2-hydroxyethyl acrylate; hydroxyalkyl acrylates such as methyl 2-(hydroxymethyl)acrylate, methyl 2-(1-hydroxyethyl)acrylate, ethyl 2-(hydroxymethyl)acrylate, and n-, i-, or t-butyl 2-(hydroxymethyl)acrylate; Unsaturated acids such as methacrylic acid and acrylic acid; Halogenated styrenes such as chlorostyrene and bromostyrene; Substituted styrenes such as vinyltoluene and α-methylstyrene; Unsaturated nitriles such as acrylonitrile and methacrylonitrile; Unsaturated acid anhydrides such as maleic anhydride and citraconic anhydride; Unsaturated imides such as phenylmaleimide and cyclohexylmaleimide; and the like monofunctional monomers. The other monofunctional monomers may be used alone or in combination of two or more kinds.

[0048] As the other copolymerization component, a polyfunctional monomer may be used. Examples of the polyfunctional monomer include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, nonaethylene glycol di(meth)acrylate, and tetradecaethylene glycol di(meth)acrylate, and other ethylene glycol or oligomers thereof in which both terminal hydroxyl groups are esterified with (meth)acrylic acid; Propylene glycol or its oligomers, both terminal hydroxyl groups of which have been esterified with (meth)acrylic acid; Esters of the hydroxyl groups of dihydric alcohols, such as neopentyl glycol di(meth)acrylate, hexanediol di(meth)acrylate, and butanediol di(meth)acrylate, with (meth)acrylic acid; Bisphenol A, alkylene oxide adducts of bisphenol A, or halogen-substituted products thereof, both terminal hydroxyl groups of which have been esterified with (meth)acrylic acid; Esters of polyhydric alcohols such as trimethylolpropane and pentaerythritol with (meth)acrylic acid, and those obtained by ring-opening addition of epoxy groups of glycidyl (meth)acrylate to the terminal hydroxyl groups of these esters; ring-opening addition of epoxy groups of glycidyl (meth)acrylate to dibasic acids such as succinic acid, adipic acid, terephthalic acid, phthalic acid, and halogen-substituted derivatives thereof, or alkylene oxide adducts thereof; Aryl (meth)acrylates; aromatic divinyl compounds such as divinylbenzene; etc. Of these, ethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, and neopentyl glycol dimethacrylate are preferably used.

[0049] The (meth)acrylic resin may be modified by a reaction between functional groups of the copolymer, such as an intrapolymer chain methanol condensation reaction between the methyl ester group of methyl (meth)acrylate and the hydroxyl group of methyl 2-(hydroxymethyl)acrylate, or an intrapolymer chain dehydration condensation reaction between the carboxyl group of (meth)acrylic acid and the hydroxyl group of methyl 2-(hydroxymethyl)acrylate.

[0050] The glass transition temperature of the (meth)acrylic resin is preferably 80° C. or more and 160° C. or less. The glass transition temperature can be controlled by adjusting the polymerization ratio of the methacrylic acid ester monomer and the acrylic acid ester monomer, the carbon chain length of each ester group and the type of functional group therein, and the polymerization ratio of the polyfunctional monomer to the total monomers.

[0051] As a means for increasing the glass transition temperature of the (meth)acrylic resin, it is also effective to introduce a ring structure into the main chain of the polymer. The ring structure is preferably a heterocyclic structure such as a cyclic acid anhydride structure, a cyclic imide structure, or a lactone structure. Specific examples of the ring structure include cyclic acid anhydride structures such as glutaric anhydride structure and succinic anhydride structure; cyclic imide structures such as glutarimide structure and succinimide structure; and lactone ring structures such as butyrolactone and valerolactone. There is a tendency that the glass transition temperature of the (meth)acrylic resin can be increased by increasing the content of the ring structure in the main chain. The cyclic acid anhydride structure and the cyclic imide structure can be introduced by a method of introducing a cyclic acid anhydride structure by copolymerizing a monomer having a cyclic structure, such as maleic anhydride or maleimide; a method of introducing a cyclic acid anhydride structure by a dehydration / demethanol condensation reaction after polymerization; or a method of introducing a cyclic imide structure by reacting an amino compound. A resin (polymer) having a lactone ring structure can be obtained by a method in which a polymer having a hydroxyl group and an ester group in the polymer chain is prepared, and then the hydroxyl group and the ester group in the obtained polymer are cyclocondensed by heating, if necessary in the presence of a catalyst such as an organic phosphorus compound, to form a lactone ring structure.

[0052] The (meth)acrylic resin and the thermoplastic resin film formed therefrom may contain additives as necessary, such as lubricants, antiblocking agents, heat stabilizers, antioxidants, antistatic agents, light resistance agents, impact resistance improvers, surfactants, etc. These additives can also be used when a thermoplastic resin other than a (meth)acrylic resin is used as the thermoplastic resin constituting the thermoplastic resin film.

[0053] The (meth)acrylic resin may contain acrylic rubber particles as an impact modifier from the viewpoint of film formability, impact resistance of the film, etc. The acrylic rubber particles are particles containing an acrylic acid ester as an essential component of an elastic polymer, and examples of the acrylic rubber particles include those having a single layer structure substantially composed of this elastic polymer alone, and those having a multilayer structure with this elastic polymer as one layer. An example of the elastic polymer is a crosslinked elastic copolymer which contains alkyl acrylate as the main component and is copolymerized with other copolymerizable vinyl monomers and crosslinkable monomers. Examples of alkyl acrylates that are the main component of the elastic polymer include those having an alkyl group with 1 to 8 carbon atoms, such as methyl acrylate, ethyl acrylate, butyl acrylate, and 2-ethylhexyl acrylate, and alkyl acrylates having an alkyl group with 4 or more carbon atoms are preferably used. Examples of other vinyl monomers copolymerizable with the alkyl acrylate include compounds having one polymerizable carbon-carbon double bond in the molecule, and more specifically, examples of such compounds include methacrylic acid esters such as methyl methacrylate; aromatic vinyl compounds such as styrene; and vinyl cyanide compounds such as acrylonitrile. Examples of the crosslinkable monomer include crosslinkable compounds having at least two polymerizable carbon-carbon double bonds in the molecule, and more specific examples thereof include (meth)acrylates of polyhydric alcohols such as ethylene glycol di(meth)acrylate and butanediol di(meth)acrylate; alkenyl esters of (meth)acrylic acid such as allyl (meth)acrylate; divinylbenzene; and the like.

[0054] A laminate of a film made of a (meth)acrylic resin containing no rubber particles and a film made of a (meth)acrylic resin containing rubber particles can also be used as the thermoplastic resin film to be attached to the polarizer 1. In addition, a (meth)acrylic resin layer is formed on one or both sides of a retardation-exhibiting layer made of a resin different from a (meth)acrylic resin, and a retardation is exhibited, and this can also be used as the thermoplastic resin film to be attached to the polarizer 1.

[0055] The thermoplastic resin film may contain an ultraviolet absorbing agent. When the polarizing plate 10 is applied to an image display device such as a liquid crystal display device, the thermoplastic resin film containing an ultraviolet absorbing agent is disposed on the viewing side of an image display element (e.g., a liquid crystal cell), thereby suppressing deterioration of the image display element due to ultraviolet rays. Examples of the ultraviolet absorbent include salicylic acid ester compounds, benzophenone compounds, benzotriazole compounds, cyanoacrylate compounds, and nickel complex compounds.

[0056] When thermoplastic resin films are attached to both sides of the polarizer 1, these thermoplastic resin films may be films made of the same thermoplastic resin or films made of different thermoplastic resins. Furthermore, these thermoplastic resin films may be the same or different in thickness, the presence or absence and type of additives, retardation properties, etc.

[0057] The second protective film 3 may have a surface treatment layer 2 (coating layer) such as a hard coat layer, an antiglare layer, an antireflection layer, a light diffusion layer, an antistatic layer, an antifouling layer, or a conductive layer on its outer surface (the surface opposite the polarizer 1).

[0058] The thickness of the thermoplastic resin film is usually 5 μm or more and 200 μm or less, preferably 10 μm or more and 120 μm or less, more preferably 10 μm or more and 85 μm or less, and further preferably 15 μm or more and 60 μm or less. The thickness of the thermoplastic resin film may be 50 μm or less, or may be 40 μm or less. Reducing the thickness of the thermoplastic resin film is advantageous for reducing the thickness of the polarizing plate 10, and furthermore, the polarizing plate with a pressure-sensitive adhesive layer, the laminated optical member, and the image display device.

[0059] The surface of the thermoplastic resin film on which the adhesive is applied may be subjected to a surface modification treatment such as saponification treatment, plasma treatment, corona treatment, primer treatment, etc. from the viewpoint of improving adhesion, or the surface modification treatment may not be performed from the viewpoint of simplifying the process. When the thermoplastic resin film is a cellulose acetate resin film, it is preferable to perform a saponification treatment from the viewpoint of improving adhesion. Examples of the saponification treatment include a method of immersing the film in an aqueous solution of an alkali such as sodium hydroxide or potassium hydroxide.

[0060] [2-3] The first protective film 4 of the pressure-sensitive adhesive layer-attached polarizing plate 25 shown in FIG. The above-mentioned thermoplastic resin films can be used as the first protective film 4 of the adhesive layer-attached polarizing plate 25 shown in Fig. 1, and among them, it is preferable to use a polar resin film. Since the first protective film 4, which is a polar resin film, is configured to be in contact with the adhesive layer 20, it is possible to easily configure an adhesive layer-attached polarizing plate that satisfies the relationship of formula (1). It is presumed that the antistatic agent contained in the adhesive layer 30 easily migrates to the first protective film 4, which is a polar resin film, and therefore an adhesive layer-attached polarizing plate that satisfies the relationship of formula (1) can be obtained.

[0061] The polar resin film is a film containing a polar resin, and the polar resin is a resin having a hydrophilic functional group in the side chain or main chain. Examples of the hydrophilic functional group include a hydroxyl group, an acetyl group, a carboxyl group, a carbonyl group, an amide group, and a cyano group. Examples of the polar resin include a cellulose resin, an acrylic resin, a melamine resin, and a polyvinyl alcohol resin, and a cellulose ester resin, which is a cellulose resin, is preferably used.

[0062] The cellulose ester resin is a resin in which at least a part of the hydroxyl group in cellulose is esterified with acetate, and may be a mixed ester in which a part is esterified with acetate and a part is esterified with another acid. The cellulose ester resin is preferably an acetyl cellulose resin. Examples of the acetyl cellulose resin include triacetyl cellulose, diacetyl cellulose, cellulose acetate propionate, and cellulose acetate butyrate. Among these, triacetyl cellulose is preferably used.

[0063] The polar resin film used as the first protective film 4 preferably has a water absorption rate of 1% or more, more preferably 3% or more, in order to easily form a polarizing plate with an adhesive layer that satisfies the relationship of formula (1). The polar resin film preferably has a water absorption rate of 8% or less. The water absorption rate is a value measured in accordance with the "Test method for water absorption rate and boiling water absorption rate of plastics" described in JIS K 7209. The size of the test piece is a square with sides of 50 mm, and the value is determined by immersing the test piece in water at a temperature of 23°C for 24 hours and then measuring the change in weight before and after immersion. The unit is %.

[0064] The polar resin film used as the first protective film 4 has a moisture permeability of 300 g / m2 at a thickness of 40 μm so that a pressure-sensitive adhesive layer-attached polarizing plate that satisfies the relationship of formula (1) can be easily formed. 2 - 24h or more is preferable, 500g / m 2 It is more preferable that the moisture permeability of the polar resin film is 5000g / m 2The moisture permeability is measured in an atmosphere at a temperature of 40°C and a humidity of 90% RH in accordance with JIS K7129:2008, Appendix B.

[0065] The polar resin film used as the first protective film 4 has a volume resistivity of 1.0×10 2 Ω cm~1.0×10 4 It is preferably Ω·cm.

[0066] [2-4] Curable resin composition cured layer The curable resin composition cured layer 5 is laminated by applying and curing a curable resin composition. In the pressure-sensitive adhesive layer polarizing plate 26 shown in Fig. 2, the curable resin composition is formed on the surface of the polarizer layer 1, and in the pressure-sensitive adhesive layer polarizing plate 27 shown in Fig. 3, the curable resin composition is formed on the surface of the first protective film 4 by applying and curing the curable resin composition.

[0067] The curable resin composition contains a curable resin such as a thermosetting resin, an ultraviolet-curable resin, an electron beam-curable resin, etc. The types of the curable resin include various resins such as polyester-based, acrylic-based, urethane-based, acryl-urethane-based, amide-based, silicone-based, silicate-based, epoxy-based, melamine-based, oxetane-based, and acryl-urethane-based resins. One or more of these curable resins can be appropriately selected and used. Among these, acrylic resins, acrylic urethane resins, and epoxy resins are preferred because they have high hardness, can be cured with ultraviolet light, and are excellent in productivity, and among these, epoxy resins and oxetane resins are preferred. UV-curable resins include UV-curable monomers, oligomers, polymers, and the like. Preferred UV-curable resins include those having a UV-polymerizable functional group, and among these, those containing epoxy-based and oxetane-based resin monomers or oligomers having two or more, particularly 3 to 6, functional groups as components.

[0068] The curable resin composition cured layer 5 is in contact with the pressure-sensitive adhesive layer 20, so that a pressure-sensitive adhesive layer-attached polarizing plate that satisfies the relationship of formula (1) can be easily constructed. It is presumed that the antistatic agent contained in the pressure-sensitive adhesive layer 30 easily migrates to the curable resin composition layer 5, and therefore a pressure-sensitive adhesive layer-attached polarizing plate that satisfies the relationship of formula (1) can be obtained.

[0069] [2-5] Manufacturing of polarizing plates Adhesives for bonding the first protective film 4 and / or the second protective film 3 (hereinafter, both may be collectively referred to as "protective films") to the polarizer 1 include water-based adhesives and active energy ray-curable adhesives. Examples of the water-based adhesive include conventionally known adhesive compositions that use a polyvinyl alcohol resin or a urethane resin as a main component.

[0070] When a polyvinyl alcohol resin is used as the main component of the adhesive, the polyvinyl alcohol resin may be a polyvinyl alcohol resin such as partially saponified polyvinyl alcohol or fully saponified polyvinyl alcohol, or a modified polyvinyl alcohol resin. The polyvinyl alcohol-based resin may be a vinyl alcohol homopolymer obtained by saponifying polyvinyl acetate, which is a homopolymer of vinyl acetate, or a polyvinyl alcohol-based copolymer obtained by saponifying a copolymer of vinyl acetate and another monomer copolymerizable therewith.

[0071] The aqueous adhesive containing the polyvinyl alcohol resin may contain a curable component or a crosslinking agent, such as a polyaldehyde, a melamine compound, a zirconia compound, a zinc compound, glyoxal, a glyoxal derivative, or a water-soluble epoxy resin, in order to improve adhesion.

[0072] An example of an aqueous adhesive containing a urethane resin as a main component is an aqueous adhesive containing a polyester ionomer type urethane resin and a compound having a glycidyloxy group. A polyester ionomer type urethane resin is a urethane resin having a polyester skeleton, into which a small amount of an ionic component (hydrophilic component) is introduced.

[0073] The active energy ray-curable adhesive is an adhesive that is cured by irradiation with active energy rays such as ultraviolet rays, visible light, electron beams, X-rays, etc. When an active energy ray-curable adhesive is used, the adhesive layer of the polarizing plate 10 is a cured layer of the adhesive.

[0074] The active energy ray curable adhesive can be an adhesive containing an epoxy compound that cures by cationic polymerization as a curable component, and is preferably an ultraviolet ray curable adhesive containing such an epoxy compound as a curable component. The epoxy compound means a compound having an average of one or more, preferably two or more, epoxy groups in the molecule. The epoxy compound may be used alone or in combination of two or more.

[0075] Examples of epoxy compounds include hydrogenated epoxy compounds (glycidyl ethers of polyols having alicyclic rings) obtained by reacting epichlorohydrin with alicyclic polyols obtained by hydrogenating the aromatic rings of aromatic polyols; aliphatic epoxy compounds such as polyglycidyl ethers of aliphatic polyhydric alcohols or their alkylene oxide adducts; and alicyclic epoxy compounds, which are epoxy compounds having one or more epoxy groups bonded to an alicyclic ring in the molecule.

[0076] The active energy ray curable adhesive may contain a radically polymerizable (meth)acrylic compound as a curable component, instead of or together with the above-mentioned epoxy compound. Examples of the (meth)acrylic compound include (meth)acryloyloxy group-containing compounds such as (meth)acrylate monomers having one or more (meth)acryloyloxy groups in the molecule; and (meth)acrylate oligomers obtained by reacting two or more functional group-containing compounds and having at least two (meth)acryloyloxy groups in the molecule.

[0077] When the active energy ray curable adhesive contains an epoxy compound that is cured by cationic polymerization as a curable component, it is preferable that the active energy ray curable adhesive contains a photocationic polymerization initiator. Examples of the photocationic polymerization initiator include aromatic diazonium salts, onium salts such as aromatic iodonium salts and aromatic sulfonium salts, and iron-allene complexes. When the active energy ray-curable adhesive contains a radical polymerizable component such as a (meth)acrylic compound, it is preferable that the active energy ray-curable adhesive contains a photoradical polymerization initiator. Examples of the photoradical polymerization initiator include acetophenone-based initiators, benzophenone-based initiators, benzoin ether-based initiators, thioxanthone-based initiators, xanthone, fluorenone, camphorquinone, benzaldehyde, and anthraquinone.

[0078] The adhesion of the polarizer 1 to the first protective film 4 or the second protective film 3 can include a process of applying an adhesive to the bonding surface of the polarizer 1 and / or the bonding surface of the protective film, or injecting an adhesive between the polarizer 1 and the thermoplastic resin film, overlapping the two films via a layer of adhesive, and pressing them from above and below using, for example, a laminating roll to bond them together.

[0079] The adhesive layer can be formed by using various coating methods, such as a doctor blade, a wire bar, a die coater, a comma coater, a gravure coater, etc. Alternatively, the adhesive may be cast between the polarizer 1 and the protective film while the polarizer 1 and the protective film are continuously fed so that the bonding surfaces of the two face inside.

[0080] Before applying the adhesive, one or both of the bonding surfaces of the polarizer 1 and the protective film may be subjected to an adhesion enhancing treatment (surface activation treatment) such as saponification treatment, corona discharge treatment, plasma treatment, flame treatment, primer treatment, anchor coating treatment, etc.

[0081] When an active energy ray-curable adhesive is used, the adhesive layer is dried as necessary, and then irradiated with active energy rays to cure the adhesive layer. The light source used for irradiating the active energy rays may be any light source capable of generating ultraviolet rays, electron beams, X-rays, etc. In particular, light sources having an emission distribution at a wavelength of 400 nm or less, such as low pressure mercury lamps, medium pressure mercury lamps, high pressure mercury lamps, ultra-high pressure mercury lamps, chemical lamps, black light lamps, microwave excited mercury lamps, metal halide lamps, etc., are preferably used.

[0082] In the obtained polarizing plate 10, the thickness of the adhesive layer formed from the aqueous adhesive is, for example, 10 nm or more and 10 μm or less, preferably 20 nm or more and 5 μm or less, more preferably 30 nm or more and 1 μm or less, and even more preferably 40 nm or more and 500 nm or less. The thickness of the adhesive layer formed from the active energy ray-curable adhesive is, for example, 10 nm or more and 20 μm or less, preferably 100 nm or more and 10 μm or less, and more preferably 500 nm or more and 5 μm or less. When protective films are attached to both sides of the polarizer 1, the two adhesive layers may have the same thickness or different thicknesses.

[0083] [2-6] Other components of polarizing plates The polarizing plate 10 can include optically functional films other than the polarizer 1 in order to impart desired optical functions, and a suitable example of such films is a retardation film. As described above, the protective film can also function as a retardation film, but a retardation film can also be laminated separately from the protective film. The retardation film can be laminated on the outer surface of the protective film via a pressure-sensitive adhesive layer or an adhesive layer, or can be laminated on the surface of the polarizer 1.

[0084] Examples of the retardation film include a birefringent film composed of a stretched film of a thermoplastic resin having light transmission properties; a film in which discotic liquid crystal or nematic liquid crystal is oriented and fixed; and a film in which the above-mentioned liquid crystal layer is formed on a substrate film. The substrate film is usually a film made of a thermoplastic resin, and an example of the thermoplastic resin is a cellulose ester resin such as triacetyl cellulose. As the thermoplastic resin for forming the birefringent film, those described for the thermoplastic resin film can be used.

[0085] Examples of other optically functional films (optical members) that can be included in the polarizing plate 10 include a light collecting plate, a brightness enhancing film, a reflective layer (reflective film), a semi-transmissive reflective layer (semi-transmissive reflective film), a light diffusing layer (light diffusing film), etc. These are generally provided when the polarizing plate 10 is a polarizing plate disposed on the rear side (backlight side) of a liquid crystal cell.

[0086] The light collecting plate is used for the purpose of controlling the optical path, and can be a prism array sheet, a lens array sheet, a dot-applied sheet, or the like.

[0087] The brightness enhancement film is used for the purpose of improving the brightness of a liquid crystal display device to which the polarizing plate 10 is applied. Specific examples include a reflective polarization separation sheet designed to generate anisotropy in reflectance by laminating a plurality of thin films having mutually different anisotropies in refractive index, and a circular polarization separation sheet in which an oriented film of a cholesteric liquid crystal polymer or a layer of the oriented liquid crystal is supported on a substrate film.

[0088] The reflective layer, semi-transmissive reflective layer, and light diffusion layer are provided to make the polarizing plate 10 a reflective, semi-transmissive, and diffusion type optical member, respectively. The reflective polarizing plate is used in a type of liquid crystal display device that reflects incident light from the viewing side to display, and since a light source such as a backlight can be omitted, it is easy to make the liquid crystal display device thinner. The semi-transmissive polarizing plate is used in a type of liquid crystal display device that acts as a reflective type in a bright place and displays using light from a backlight in a dark place. The diffusion type polarizing plate is used in a liquid crystal display device that is given light diffusion properties to suppress display defects such as moire. The reflective layer, semi-transmissive reflective layer, and light diffusion layer can be formed by a known method.

[0089] The polarizing plate 10 may include a protective film for protecting the surface (typically the surface on the viewing side) opposite to the side on which the pressure-sensitive adhesive layer 20 is laminated. After the pressure-sensitive adhesive layer-attached polarizing plate is attached to an optical member such as an image display element, the protective film is peeled off and removed together with the pressure-sensitive adhesive layer that it has.

[0090] The protective film is composed of, for example, a base film and an adhesive layer laminated thereon. The resin constituting the base film may be, for example, a thermoplastic resin such as a polyethylene-based resin such as polyethylene, a polypropylene-based resin such as polypropylene, a polyester-based resin such as polyethylene terephthalate or polyethylene naphthalate, or a polycarbonate-based resin. A polyester-based resin such as polyethylene terephthalate is preferred.

[0091] [3] Adhesive layer The pressure-sensitive adhesive layer 20 constituting the pressure-sensitive adhesive layer-attached polarizing plates 25, 26, and 27 is formed from a pressure-sensitive adhesive composition.

[0092] [3-1] (Meth)acrylic resin The pressure-sensitive adhesive composition preferably contains a (meth)acrylic resin from the viewpoints of the optical properties (transparency, polarization properties, etc.) of the pressure-sensitive adhesive layer-attached polarizing plate, the adhesion between the pressure-sensitive adhesive layer-attached polarizing plate and other optical members, etc. The pressure-sensitive adhesive composition may contain one or more (meth)acrylic resins. In this specification, "(meth)acrylic" means acrylic and / or methacrylic, and the same applies to "(meth)" in (meth)acrylate, etc. The heat resistance and durability refers to resistance to defects such as lifting or peeling at the interface between the pressure-sensitive adhesive layer and other optical components, and foaming of the pressure-sensitive adhesive layer, which may occur when the laminated optical component is placed under high temperatures or in an environment where high and low temperatures are repeatedly changed.

[0093] From the viewpoints of the optical properties (transparency, polarization properties, etc.) of the pressure-sensitive adhesive layer-attached polarizing plate, the adhesion between the pressure-sensitive adhesive layer and other optical members, etc., the (meth)acrylic resin is represented by the following formula (I):

[0094] TIFF0007628396000001.tif27136 It is preferable that the polymer contains, as a main component, a structural unit derived from a (meth)acrylic acid ester represented by the following formula: The term "main component" means that the content of the structural unit in all structural units constituting the (meth)acrylic resin is 50% by mass or more.

[0095] In the above formula (I), R 1 represents a hydrogen atom or a methyl group, R 2 represents an alkyl group having from 1 to 14 carbon atoms which may be substituted with an alkoxy group having from 1 to 10 carbon atoms, or an aralkyl group having from 7 to 21 carbon atoms which may be substituted with an alkoxy group having from 1 to 10 carbon atoms. When the aralkyl group is substituted with an alkoxy group, the number of carbon atoms in the aralkyl group is the number of carbon atoms excluding the carbon atoms of the alkoxy group. R 2 is preferably an alkyl group having 1 to 14 carbon atoms which may be substituted with an alkoxy group having 1 to 10 carbon atoms, and more preferably an alkyl group having 1 to 14 carbon atoms which is not substituted with an alkoxy group.

[0096] Examples of the (meth)acrylic acid ester represented by formula (I) include (meth)acrylic acid alkyl esters having a linear alkyl ester moiety, such as methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, n-octyl (meth)acrylate, and lauryl (meth)acrylate; and (meth)acrylic acid alkyl esters having a branched alkyl ester moiety, such as isobutyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, and isooctyl (meth)acrylate.

[0097] R 2 is an alkyl group substituted with an alkoxy group, i.e., R 2 Examples of the (meth)acrylic acid ester represented by formula (I) in which is an alkoxyalkyl group include 2-methoxyethyl (meth)acrylate and ethoxymethyl (meth)acrylate. R 2 Examples of the (meth)acrylic acid ester represented by formula (I) in which is an aralkyl group having 7 or more and 21 or less carbon atoms include benzyl (meth)acrylate.

[0098] The (meth)acrylic acid ester represented by formula (I) may be used alone or in combination of two or more kinds. Among them, the (meth)acrylic acid ester preferably contains n-butyl acrylate. The (meth)acrylic resin contains, among all the constituent units constituting the resin, preferably 50% by mass or more, more preferably 55% by mass or more, of constituent units derived from n-butyl acrylate. The content of the constituent units derived from n-butyl acrylate among all the constituent units constituting the (meth)acrylic resin is usually 90% by mass or less, preferably 85% by mass or less, more preferably 80% by mass or less, and even more preferably 75% by mass or less. In addition to n-butyl acrylate, other (meth)acrylic acid esters represented by formula (I) may also be used in combination. For example, the (meth)acrylic resin preferably contains a structural unit derived from n-butyl acrylate and a structural unit derived from methyl acrylate. When the (meth)acrylic resin contains a structural unit derived from n-butyl acrylate and a structural unit derived from methyl acrylate, the content of the structural unit derived from n-butyl acrylate is as described above, and the content of the structural unit derived from methyl acrylate is usually 1% by mass or more and 50% by mass or less, preferably 5% by mass or more and 45% by mass or less, and more preferably 10% by mass or more and 40% by mass or less, of all the structural units constituting the (meth)acrylic resin.

[0099] The content of the structural unit derived from the (meth)acrylic acid ester represented by formula (I) is, from the viewpoints of the optical properties (transparency, polarization properties, etc.) of the pressure-sensitive adhesive layer-attached polarizing plate, the adhesion between the pressure-sensitive adhesive layer and other optical components, and the like, preferably from 60 mass% to less than 100 mass%, more preferably from 70 mass% to 99.9 mass%, and even more preferably from 80 mass% to 99.6 mass%, of all the structural units constituting the (meth)acrylic resin.

[0100] The (meth)acrylic resin may contain a structural unit derived from a (meth)acrylic monomer having a hydroxyl group. Examples of the (meth)acrylic monomer having a hydroxyl group include (meth)acrylic acid esters having a hydroxyl group. Examples of (meth)acrylic acid esters having a hydroxyl group include 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-(2-hydroxyethoxy)ethyl (meth)acrylate, 2- or 3-chloro-2-hydroxypropyl (meth)acrylate, and diethylene glycol mono(meth)acrylate.

[0101] From the viewpoints of processability of the pressure-sensitive adhesive layer and adhesion to other optical components, the content of structural units derived from (meth)acrylic monomers having a hydroxyl group is preferably from 0.1% by mass to 5% by mass, and more preferably from 0.5% by mass to 4% by mass, of all structural units constituting the (meth)acrylic resin.

[0102] The (meth)acrylic resin may contain a structural unit derived from a monomer having a polar functional group other than the (meth)acrylic monomer having a hydroxyl group. The monomer having a polar functional group is preferably a (meth)acrylic monomer having a polar functional group. Examples of the polar functional group contained in the monomer having another polar functional group include a carboxyl group (free carboxyl group), an amino group, a heterocyclic group (for example, an epoxy group), and an amide group.

[0103] Other monomers having polar functional groups include: Monomers having a carboxyl group, such as (meth)acrylic acid and β-carboxyethyl (meth)acrylate ((meth)acrylic monomers having a carboxyl group); Monomers having a heterocyclic group, such as (meth)acryloylmorpholine, vinylcaprolactam, N-vinyl-2-pyrrolidone, vinylpyridine, tetrahydrofurfuryl (meth)acrylate, caprolactone-modified tetrahydrofurfuryl (meth)acrylate, 3,4-epoxycyclohexylmethyl (meth)acrylate, glycidyl (meth)acrylate, and 2,5-dihydrofuran; Examples of the monomer include a monomer having an amino group different from a heterocycle, such as aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, and dimethylaminopropyl (meth)acrylate. The monomer having another polar functional group may be used alone or in combination of two or more kinds.

[0104] The content of structural units derived from monomers having other polar functional groups is preferably from 0.1% by mass to 5% by mass, and more preferably from 0.5% by mass to 3% by mass, of all structural units constituting the (meth)acrylic resin, from the viewpoint of adhesion between the pressure-sensitive adhesive layer and other optical components, etc.

[0105] The (meth)acrylic resin may further contain a structural unit derived from a monomer having one olefinic double bond and at least one aromatic ring in the molecule (excluding those corresponding to the above formula (I) or the above monomer having a polar functional group). Inclusion of a structural unit derived from a monomer having one olefinic double bond and at least one aromatic ring in the molecule can be advantageous in terms of effectively suppressing the occurrence of white spots and color unevenness in laminated optical components.

[0106] The monomer having one olefinic double bond and at least one aromatic ring in the molecule includes a (meth)acrylic monomer having an aromatic ring. Examples of the (meth)acrylic monomer having an aromatic ring include neopentyl glycol benzoate (meth)acrylate and the monomer represented by the following formula (II):

[0107] TIFF0007628396000002.tif23114 Examples of the (meth)acrylic acid ester include an aryloxyalkyl group-containing (meth)acrylic acid ester represented by the following formula: embedded image and preferably an aryloxyalkyl group-containing (meth)acrylic acid ester.

[0108] In formula (II), R 3 represents a hydrogen atom or a methyl group, i represents an integer of 1 to 8, R 4 R represents a hydrogen atom, an alkyl group, an aralkyl group, or an aryl group. 4 When it is an alkyl group, it may have about 1 or more and 9 or less carbon atoms; when it is an aralkyl group, it may have about 7 or more and 11 or less carbon atoms; and when it is an aryl group, it may have about 6 or more and 10 or less carbon atoms.

[0109] R in formula (II) 4 Examples of the alkyl group having 1 to 9 carbon atoms in the above formula (1) include a methyl group, a butyl group, a nonyl group, etc., examples of the aralkyl group having 7 to 11 carbon atoms in the above formula (1) include a benzyl group, a phenethyl group, a naphthylmethyl group, etc., and examples of the aryl group having 6 to 10 carbon atoms in the above formula (1) include a phenyl group, a tolyl group, a naphthyl group, etc.

[0110] Specific examples of the phenoxyethyl group-containing (meth)acrylic acid ester represented by formula (II) include, for example, 2-phenoxyethyl (meth)acrylate, 2-(2-phenoxyethoxy)ethyl (meth)acrylate, (meth)acrylic acid ester of ethylene oxide-modified nonylphenol, and 2-(o-phenylphenoxy)ethyl (meth)acrylate. The phenoxyethyl group-containing (meth)acrylic acid esters may be used alone or in combination of two or more kinds. Among these, the phenoxyethyl group-containing (meth)acrylic acid ester preferably contains one or more selected from the group consisting of 2-phenoxyethyl (meth)acrylate, 2-(o-phenylphenoxy)ethyl (meth)acrylate, and 2-(2-phenoxyethoxy)ethyl (meth)acrylate, and more preferably contains one or two selected from the group consisting of 2-(o-phenylphenoxy)ethyl (meth)acrylate and 2-(2-phenoxyethoxy)ethyl (meth)acrylate.

[0111] From the viewpoint of effectively suppressing the occurrence of white spots and color unevenness in the laminated optical component, the content of the structural units derived from a monomer having one olefinic double bond and at least one aromatic ring in the molecule is preferably from 1 mass % to 20 mass %, and more preferably from 5 mass % to 15 mass %, of all the structural units constituting the (meth)acrylic resin.

[0112] The (meth)acrylic resin may contain a constituent unit derived from a monomer (hereinafter also referred to as "other monomer") other than the (meth)acrylic acid ester of formula (I) described above, the monomer having a polar functional group, and the monomer having one olefinic double bond and at least one aromatic ring in the molecule. Examples of other monomers include structural units derived from (meth)acrylic acid esters having an alicyclic structure in the molecule, structural units derived from styrene-based monomers, structural units derived from vinyl-based monomers, structural units derived from monomers having multiple (meth)acryloyl groups in the molecule, and structural units derived from (meth)acrylamide monomers. The other monomers may be used alone or in combination of two or more. The inclusion of a structural unit derived from another monomer, particularly a structural unit derived from a (meth)acrylamide monomer, can be advantageous in terms of improving the adhesion between the pressure-sensitive adhesive layer and other optical members.

[0113] The alicyclic structure in the (meth)acrylic acid ester having an alicyclic structure in the molecule is a cycloparaffin structure having usually 5 or more, preferably about 5 to 7 carbon atoms. Examples of (meth)acrylic acid esters having an alicyclic structure include isobornyl (meth)acrylate, cyclohexyl (meth)acrylate, dicyclopentanyl (meth)acrylate, cyclododecyl (meth)acrylate, methylcyclohexyl (meth)acrylate, trimethylcyclohexyl (meth)acrylate, t-butylcyclohexyl (meth)acrylate, cyclohexylphenyl (meth)acrylate, and cyclohexyl α-ethoxyacrylate.

[0114] Examples of styrene-based monomers include styrene; alkyl styrenes such as methylstyrene, dimethylstyrene, trimethylstyrene, ethylstyrene, diethylstyrene, triethylstyrene, propylstyrene, butylstyrene, hexylstyrene, heptylstyrene, and octylstyrene; halogenated styrenes such as fluorostyrene, chlorostyrene, bromostyrene, dibromostyrene, and iodostyrene; nitrostyrene, acetylstyrene, methoxystyrene, and divinylbenzene.

[0115] Examples of vinyl monomers include fatty acid vinyl esters such as vinyl acetate, vinyl propionate, vinyl butyrate, vinyl 2-ethylhexanoate, and vinyl laurate; vinyl halides such as vinyl chloride and vinyl bromide; vinylidene halides such as vinylidene chloride; nitrogen-containing aromatic vinyls such as vinylpyridine, vinylpyrrolidone, and vinylcarbazole; conjugated diene monomers such as butadiene, isoprene, and chloroprene; acrylonitrile, methacrylonitrile, and the like.

[0116] Examples of monomers having multiple (meth)acryloyl groups in the molecule include monomers having two (meth)acryloyl groups in the molecule, such as 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, and tripropylene glycol di(meth)acrylate; and monomers having three (meth)acryloyl groups in the molecule, such as trimethylolpropane tri(meth)acrylate.

[0117] Examples of (meth)acrylamide monomers include N-methylol (meth)acrylamide, N-(2-hydroxyethyl) (meth)acrylamide, N-(3-hydroxypropyl) (meth)acrylamide, N-(4-hydroxybutyl) (meth)acrylamide, N-(5-hydroxypentyl) (meth)acrylamide, N-(6-hydroxyhexyl) (meth)acrylamide, N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, and N-isopropyl (meth)acrylamide. propyl(meth)acrylamide, N-(3-dimethylaminopropyl)(meth)acrylamide, N-(1,1-dimethyl-3-oxobutyl)(meth)acrylamide, N-[2-(2-oxo-1-imidazolidinyl)ethyl](meth)acrylamide, 2-acryloylamino-2-methyl-1-propanesulfonic acid, N-(methoxymethyl)acrylamide, N-(ethoxymethyl)(meth)acrylamide, N-(propoxymethyl)(meth)acrylamide, N-(1- Methylethoxymethyl)(meth)acrylamide, N-(1-methylpropoxymethyl)(meth)acrylamide, N-(2-methylpropoxymethyl)(meth)acrylamide [alias: N-(isobutoxymethyl)(meth)acrylamide], N-(butoxymethyl)(meth)acrylamide, N-(1,1-dimethylethoxymethyl)(meth)acrylamide, N-(2-methoxyethyl)(meth)acrylamide, N-(2-ethoxyethyl)(meth)acrylamide, N- These include (2-propoxyethyl)(meth)acrylamide, N-[2-(1-methylethoxy)ethyl](meth)acrylamide, N-[2-(1-methylpropoxy)ethyl](meth)acrylamide, N-[2-(2-methylpropoxy)ethyl](meth)acrylamide (also known as N-(2-isobutoxyethyl)(meth)acrylamide), N-(2-butoxyethyl)(meth)acrylamide, N-[2-(1,1-dimethylethoxy)ethyl](meth)acrylamide, etc. Among these, N-(methoxymethyl)acrylamide, N-(ethoxymethyl)acrylamide, N-(propoxymethyl)acrylamide, N-(butoxymethyl)acrylamide, and N-(2-methylpropoxymethyl)acrylamide are preferably used.

[0118] From the viewpoint of adhesion between the pressure-sensitive adhesive layer and other optical members, the (meth)acrylamide monomer is preferably an alkyl(meth)acrylamide monomer which may be substituted with an alkoxy group. In the alkyl(meth)acrylamide monomer which may be substituted with an alkoxy group, the carbon number of the alkoxy group is preferably from 1 to 10, and the carbon number of the alkyl group is preferably from 1 to 14. When the alkyl group is substituted with an alkoxy group, the carbon number of the alkyl group is the carbon number excluding the carbon atoms of the alkoxy group. As the alkyl(meth)acrylamide monomer which may be substituted with an alkoxy group, there is used the alkyl(meth)acrylamide monomer represented by the following formula (III):

[0119] TIFF0007628396000003.tif23114 Examples of the alkoxyalkyl (meth)acrylamide monomer include those represented by the following formula: In formula (III), R 5 represents a hydrogen atom or a methyl group, R 6 represents an alkyl group having 1 to 14 carbon atoms. n represents an integer of 1 to 8. Examples of the alkyl group include a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a tert-butyl group, an n-hexyl group, an n-heptyl group, and an n-octyl group. n is preferably 1 or more and 6 or less.

[0120] The content of structural units derived from other monomers (particularly (meth)acrylamide monomers) is, from the viewpoint of adhesion between the pressure-sensitive adhesive layer and other optical components, preferably from 0.1 mass% to 20 mass%, more preferably from 0.2 mass% to 10 mass%, and even more preferably from 0.3 mass% to 5 mass%, of all structural units constituting the (meth)acrylic resin.

[0121] From the viewpoint of adhesion between the pressure-sensitive adhesive layer and other optical components, the (meth)acrylic resin preferably contains a structural unit derived from a (meth)acrylic monomer having a carboxyl group and a structural unit derived from an alkoxyalkyl (meth)acrylamide monomer. From the viewpoint of adhesion between the pressure-sensitive adhesive layer and other optical components, the total content of the structural units derived from the (meth)acrylic monomer having a carboxyl group and the structural units derived from the alkoxyalkyl (meth)acrylamide monomer is preferably from 0.1% by mass to 15% by mass, more preferably from 0.2% by mass to 10% by mass, and even more preferably from 0.3% by mass to 4% by mass, of all the structural units constituting the (meth)acrylic resin.

[0122] The (meth)acrylic resin preferably has a weight average molecular weight (Mw) in the range of 500,000 to 2,000,000, and more preferably 600,000 to 1,800,000, as calculated using standard polystyrene standards by gel permeation chromatography (GPC). A pressure-sensitive adhesive composition containing a (meth)acrylic resin having an Mw within the above range can be advantageous from the viewpoint of ensuring the handleability of the (meth)acrylic resin during preparation of the pressure-sensitive adhesive composition. The molecular weight distribution, which is expressed by the ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn), is usually about 2 or more and 10 or less, and preferably 3 or more and 8 or less.

[0123] The (meth)acrylic resin can be produced by known methods such as solution polymerization, bulk polymerization, suspension polymerization, and emulsion polymerization. A polymerization initiator is usually used in the production of the (meth)acrylic resin. The polymerization initiator can be used in an amount of about 0.001 parts by mass or more and about 5 parts by mass or less relative to a total of 100 parts by mass of all monomers used in the production of the (meth)acrylic resin. The (meth)acrylic resin may also be produced by a method in which polymerization is promoted by active energy rays such as ultraviolet rays.

[0124] As the polymerization initiator, a thermal polymerization initiator, a photopolymerization initiator, or the like is used. An example of the photopolymerization initiator is 4-(2-hydroxyethoxy)phenyl(2-hydroxy-2-propyl)ketone. Examples of the thermal polymerization initiator include azo compounds such as 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethyl-4-methoxyvaleronitrile), dimethyl-2,2'-azobis(2-methylpropionate), and 2,2'-azobis(2-hydroxymethylpropionitrile); lauryl peroxide; Examples of the peroxide include organic peroxides such as tert-butyl hydroperoxide, benzoyl peroxide, tert-butyl peroxybenzoate, cumene hydroperoxide, diisopropyl peroxydicarbonate, dipropyl peroxydicarbonate, tert-butyl peroxyneodecanoate, tert-butyl peroxypivalate, and (3,5,5-trimethylhexanoyl) peroxide; and inorganic peroxides such as potassium persulfate, ammonium persulfate, and hydrogen peroxide. Furthermore, a redox initiator using a peroxide and a reducing agent in combination can also be used as the polymerization initiator.

[0125] Among the above methods, the solution polymerization method is preferred as a method for producing a (meth)acrylic resin. One example of the solution polymerization method is to mix the monomer and organic solvent to be used, add a thermal polymerization initiator under a nitrogen atmosphere, and stir for about 3 hours to 15 hours at about 40°C to 90°C, preferably about 50°C to 80°C. In order to control the reaction, the monomer and the thermal polymerization initiator may be added continuously or intermittently during polymerization, or may be added in a state dissolved in an organic solvent. Examples of organic solvents include aromatic hydrocarbons such as toluene and xylene; esters such as ethyl acetate and butyl acetate; aliphatic alcohols such as propyl alcohol and isopropyl alcohol; and ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone.

[0126] [3-2] Crosslinking agent The pressure-sensitive adhesive composition may further contain a crosslinking agent. The crosslinking agent is a compound that reacts with a polar functional group in the (meth)acrylic resin to crosslink the (meth)acrylic resin. The crosslinking agent may be selected from an isocyanate-based compound, an epoxy-based compound, an aziridine-based compound, a metal chelate-based compound, and the like. Of these, the isocyanate-based compounds, epoxy-based compounds and aziridine-based compounds have at least two functional groups in the molecule that can react with polar functional groups in the (meth)acrylic resin. The crosslinking agent may be used alone or in combination of two or more kinds.

[0127] An isocyanate compound is a compound having at least two isocyanato groups (-NCO) in the molecule. Examples of isocyanate compounds include tolylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, naphthalene diisocyanate, triphenylmethane triisocyanate, etc. In addition, adducts obtained by reacting these isocyanate compounds with polyols such as glycerol and trimethylolpropane, and dimers, trimers, etc. of isocyanate compounds can also serve as crosslinking agents. Two or more kinds of isocyanate compounds can be used in combination.

[0128] An epoxy compound is a compound having at least two epoxy groups in the molecule. Examples of epoxy compounds include bisphenol A type epoxy resins, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, glycerin diglycidyl ether, glycerin triglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane triglycidyl ether, N,N-diglycidylaniline, N,N,N',N'-tetraglycidyl-m-xylylenediamine, and 1,3-bis(N,N'-diglycidylaminomethyl)cyclohexane. Two or more kinds of epoxy compounds can be used in combination.

[0129] An aziridine compound is a compound that has at least two three-membered ring skeletons, each of which is composed of one nitrogen atom and two carbon atoms and is also called ethyleneimine. Examples of the aziridine compounds include diphenylmethane-4,4'-bis(1-aziridinecarboxamide), toluene-2,4-bis(1-aziridinecarboxamide), triethylenemelamine, isophthaloylbis-1-(2-methylaziridine), tris-1-aziridinylphosphine oxide, hexamethylene-1,6-bis(1-aziridinecarboxamide), trimethylolpropane-tris-β-aziridinylpropionate, and tetramethylolmethane-tris-β-aziridinylpropionate. Two or more aziridine compounds may be used in combination.

[0130] Examples of the metal chelate compound include compounds in which acetylacetone or ethyl acetoacetate is coordinated with a polyvalent metal such as aluminum, iron, copper, zinc, tin, titanium, nickel, antimony, magnesium, vanadium, chromium, or zirconium. Two or more metal chelate compounds may be used in combination.

[0131] Among these, isocyanate-based compounds can be advantageous in terms of improving the adhesion between the pressure-sensitive adhesive layer and other optical members. Among the isocyanate compounds, xylylene diisocyanate, tolylene diisocyanate, or hexamethylene diisocyanate; adducts obtained by reacting these isocyanate compounds with polyols such as glycerol or trimethylolpropane; dimers, trimers, etc. of these isocyanate compounds, or mixtures thereof; and mixtures of two or more of the above-mentioned isocyanate compounds are preferably used. Suitable isocyanate compounds include tolylene diisocyanate, an adduct obtained by reacting tolylene diisocyanate with a polyol, a dimer of tolylene diisocyanate, and a trimer of tolylene diisocyanate, as well as hexamethylene diisocyanate, an adduct obtained by reacting hexamethylene diisocyanate with a polyol, a dimer of hexamethylene diisocyanate, and a trimer of hexamethylene diisocyanate.

[0132] The content of the crosslinking agent in the pressure-sensitive adhesive composition is usually 0 to 5 parts by mass, preferably 0 to 2 parts by mass, per 100 parts by mass of the (meth)acrylic resin. When the pressure-sensitive adhesive composition contains a crosslinking agent, the lower limit of the content is, for example, 0.05 parts by mass, per 100 parts by mass of the (meth)acrylic resin.

[0133] [3-3] Antistatic agents The pressure-sensitive adhesive composition contains an antistatic agent for imparting antistatic properties to the pressure-sensitive adhesive layer 20. The antistatic agent is preferably an ionic compound. The ionic compound is a compound having an inorganic cation or an organic cation and an inorganic anion or an organic anion. Two or more ionic compounds may be used.

[0134] Examples of inorganic cations include lithium cations [Li + 〕, sodium cation [Na + 〕, potassium cation [K + ] and beryllium cations [Be 2+ ], magnesium cation [Mg 2+ ], calcium cation [Ca2+ ] and the like.

[0135] Examples of the organic cation include an imidazolium cation, a pyridinium cation, a pyrrolidinium cation, an ammonium cation, a sulfonium cation, and a phosphonium cation.

[0136] Among the above-mentioned cationic components, organic cationic components are preferably used because they have excellent compatibility with the pressure-sensitive adhesive composition. Among the organic cationic components, pyridinium cations and imidazolium cations are particularly preferably used because they are less likely to be charged when the separation film provided on the pressure-sensitive adhesive layer 20 is peeled off.

[0137] The inorganic anion is, for example, a chloride anion [Cl - ], bromide anion [Br - 〕, iodide anion〔I - ], tetrachloroaluminate anion [AlCl4 - 〕, heptachlorodialuminate anion〔Al2Cl7 - 〕, tetrafluoroborate anion [BF4 - 〕, hexafluorophosphate anion〔PF6 - 〕, perchlorate anion〔ClO4 - 〕, nitrate anion〔NO3 - 〕, hexafluoroarsenate anion〔AsF6 - 〕, hexafluoroantimonate anion〔SbF6 - ], hexafluoroniobate anion [NbF6 - ], hexafluorotantalate anion [TaF6 - 〕, dicyanamide anion [(CN)2N - ] etc.

[0138] The organic anion is, for example, an acetate anion [CHCOO - 〕, trifluoroacetate anion〔CF3COO -〕, methanesulfonate anion〔CH3SO3 - 〕, trifluoromethanesulfonate anion〔CF3SO3 - 〕, p-toluenesulfonate anion〔p-CH3C6H4SO3 - 〕, bis(fluorosulfonyl)imide anion [(FSO2)2N - 〕, bis(trifluoromethanesulfonyl)imide anion [(CF3SO2)2N - 〕, tris(trifluoromethanesulfonyl)methanide anion〔(CF3SO2)3C - 〕, dimethylphosphinate anion〔(CH3)2POO - 〕, (poly)hydrofluorofluoride anion〔F(HF) n - 〕(n is 1 to 3), thiocyanate anion [SCN - 〕, perfluorobutanesulfonate anion〔C4F9SO3 - 〕, bis(pentafluoroethanesulfonyl)imide anion [(C2F5SO2)2N - 〕, perfluorobutanoate anion〔C3F7COO - 〕, (trifluoromethanesulfonyl)(trifluoromethanecarbonyl)imide anion [(CF3SO2)(CF3CO)N - 〕, perfluoropropane-1,3-disulfonate anion〔 - O3S(CF2)3SO3 - 〕, carbonate anion〔CO3 2- ] etc.

[0139] Among the above-mentioned anion components, anion components containing fluorine atoms are preferably used because they provide ionic compounds with excellent antistatic properties. Examples of the anion components containing fluorine atoms include bis(fluorosulfonyl)imide anion, hexafluorophosphate anion, and bis(trifluoromethanesulfonyl)imide anion.

[0140] Specific examples of the ionic compound can be selected from the combinations of the above-mentioned cationic components and anionic components. Examples of ionic compounds having organic cations are shown below, classified according to the structure of the organic cation.

[0141] Pyridinium salts: N-Hexylpyridinium hexafluorophosphate, N-octylpyridinium hexafluorophosphate, N-octyl-4-methylpyridinium hexafluorophosphate, N-butyl-4-methylpyridinium hexafluorophosphate, N-Decylpyridinium bis(fluorosulfonyl)imide, N-dodecylpyridinium bis(fluorosulfonyl)imide, N-Tetradecylpyridinium bis(fluorosulfonyl)imide, N-Hexadecylpyridinium bis(fluorosulfonyl)imide, N-dodecyl-4-methylpyridinium bis(fluorosulfonyl)imide, N-tetradecyl-4-methylpyridinium bis(fluorosulfonyl)imide, N-Hexadecyl-4-methylpyridinium bis(fluorosulfonyl)imide, N-benzyl-2-methylpyridinium bis(fluorosulfonyl)imide, N-benzyl-4-methylpyridinium bis(fluorosulfonyl)imide, N-hexylpyridinium bis(trifluoromethanesulfonyl)imide, N-Octylpyridinium bis(trifluoromethanesulfonyl)imide, N-octyl-4-methylpyridinium bis(trifluoromethanesulfonyl)imide, N-Butyl-4-methylpyridinium bis(trifluoromethanesulfonyl)imide.

[0142] Imidazolium salts: 1-ethyl-3-methylimidazolium hexafluorophosphate, 1-ethyl-3-methylimidazolium p-toluenesulfonate, 1-ethyl-3-methylimidazolium bis(fluorosulfonyl)imide, 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, 1-butyl-3-methylimidazolium methanesulfonate, 1-Butyl-3-methylimidazolium bis(fluorosulfonyl)imide.

[0143] Pyrrolidinium salts: N-butyl-N-methylpyrrolidinium hexafluorophosphate, N-butyl-N-methylpyrrolidinium bis(fluorosulfonyl)imide, N-Butyl-N-methylpyrrolidinium bis(trifluoromethanesulfonyl)imide.

[0144] Quaternary ammonium salts: tetrabutylammonium hexafluorophosphate, tetrabutylammonium p-toluenesulfonate, (2-hydroxyethyl)trimethylammonium bis(trifluoromethanesulfonyl)imide, (2-Hydroxyethyl)trimethylammonium dimethylphosphinate.

[0145] Examples of ionic compounds having inorganic cations are shown below.

[0146] Lithium bromide, Lithium iodide, lithium tetrafluoroborate, lithium hexafluorophosphate, lithium thiocyanate, Lithium Perchlorate, lithium trifluoromethanesulfonate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(pentafluoroethanesulfonyl)imide, lithium tris(trifluoromethanesulfonyl)methanide, Lithium p-toluenesulfonate, sodium hexafluorophosphate, sodium bis(fluorosulfonyl)imide, sodium bis(trifluoromethanesulfonyl)imide, sodium p-toluenesulfonate, potassium hexafluorophosphate, potassium bis(fluorosulfonyl)imide, potassium bis(trifluoromethanesulfonyl)imide, Potassium p-toluenesulfonate.

[0147] The ionic compound is preferably solid at room temperature. An ionic compound that is solid at room temperature can maintain antistatic performance for a long period of time compared to the case of using an ionic compound that is liquid at room temperature. From the viewpoint of long-term stability of antistatic properties, the ionic compound preferably has a melting point of 30°C or higher, more preferably 35°C or higher. On the other hand, if the melting point is too high, the compatibility with the (meth)acrylic resin becomes poor, so the melting point of the ionic compound is preferably 90°C or lower, more preferably 70°C or lower, and even more preferably less than 50°C.

[0148] The content of the ionic compound in the adhesive composition is preferably 0.1 parts by mass or more and 10 parts by mass or less, more preferably 0.2 parts by mass or more and 10 parts by mass or less, even more preferably 0.2 parts by mass or more and 9 parts by mass or less, and particularly preferably 1 part by mass or more and 8 parts by mass or less, relative to 100 parts by mass of the (meth)acrylic resin. The content of the ionic compound of 0.2 parts by mass or more is advantageous for improving antistatic performance, and the content of 8 parts by mass or less is advantageous for the impact resistance of the adhesive layer 20. When the content of the ionic compound in the adhesive composition is 2 parts by mass or more, particularly 3 parts by mass or more, peeling of the adhesive layer-attached polarizing plate due to physical impact tends to occur over time, but according to the present invention, peeling can be suppressed even when the content of the ionic compound is 2 parts by mass or more or 3 parts by mass or more.

[0149] The antistatic agent in the pressure-sensitive adhesive layer may reduce the adhesion between the pressure-sensitive adhesive layer of the pressure-sensitive adhesive layer-attached polarizing plate and other optical members over time. By configuring the pressure-sensitive adhesive layer-attached polarizing plate so as to satisfy formula (1), it is possible to suppress the decrease in adhesion over time.

[0150] [3-4] Silane compounds The pressure-sensitive adhesive composition may further contain a silane compound, which can enhance the adhesion between the pressure-sensitive adhesive layer 20 and an optical member such as a glass substrate.

[0151] Examples of the silane compound include vinyltrimethoxysilane, vinyltriethoxysilane, vinyltris(2-methoxyethoxy)silane, N-(2-aminoethyl)-3-aminopropylmethyldimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-chloropropylmethyldimethoxysilane, 3-chloropropyltrimethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropyldimethoxymethylsilane, and 3-glycidoxypropylethoxydimethylsilane. Two or more silane compounds may be used.

[0152] The silane compound may be of the silicone oligomer type. When the silicone oligomer is expressed in the form of a (monomeric) oligomer, for example, the following can be mentioned:

[0153] 3-mercaptopropyltrimethoxysilane-tetramethoxysilane copolymer, 3-mercaptopropyltrimethoxysilane-tetraethoxysilane copolymer, 3-mercaptopropyltriethoxysilane-tetramethoxysilane copolymer, 3-Mercaptopropyltriethoxysilane-Tetraethoxysilane Copolymer mercaptopropyl group-containing copolymers such as; mercaptomethyltrimethoxysilane-tetramethoxysilane copolymer, mercaptomethyltrimethoxysilane-tetraethoxysilane copolymer, mercaptomethyltriethoxysilane-tetramethoxysilane copolymer, Mercaptomethyltriethoxysilane-tetraethoxysilane copolymer mercaptomethyl group-containing copolymers such as 3-glycidoxypropyltrimethoxysilane-tetramethoxysilane copolymer, 3-glycidoxypropyltrimethoxysilane-tetraethoxysilane copolymer, 3-glycidoxypropyltriethoxysilane-tetramethoxysilane copolymer, 3-glycidoxypropyltriethoxysilane-tetraethoxysilane copolymer, 3-glycidoxypropylmethyldimethoxysilane-tetramethoxysilane copolymer, 3-glycidoxypropylmethyldimethoxysilane-tetraethoxysilane copolymer, 3-glycidoxypropylmethyldiethoxysilane-tetramethoxysilane copolymer, Copolymers containing 3-glycidoxypropyl groups, such as 3-glycidoxypropylmethyldiethoxysilane-tetraethoxysilane copolymer; 3-methacryloyloxypropyltrimethoxysilane-tetramethoxysilane copolymer, 3-methacryloyloxypropyltrimethoxysilane-tetraethoxysilane copolymer, 3-methacryloyloxypropyltriethoxysilane-tetramethoxysilane copolymer, 3-methacryloyloxypropyltriethoxysilane-tetraethoxysilane copolymer, 3-methacryloyloxypropylmethyldimethoxysilane-tetramethoxysilane copolymer, 3-methacryloyloxypropylmethyldimethoxysilane-tetraethoxysilane copolymer, 3-methacryloyloxypropylmethyldiethoxysilane-tetramethoxysilane copolymer, 3-Methacryloyloxypropylmethyldiethoxysilane-tetraethoxysilane copolymer Methacryloyloxypropyl group-containing copolymers such as 3-acryloyloxypropyltrimethoxysilane-tetramethoxysilane copolymer, 3-acryloyloxypropyltrimethoxysilane-tetraethoxysilane copolymer, 3-acryloyloxypropyltriethoxysilane-tetramethoxysilane copolymer, 3-acryloyloxypropyltriethoxysilane-tetraethoxysilane copolymer, 3-acryloyloxypropylmethyldimethoxysilane-tetramethoxysilane copolymer, 3-acryloyloxypropylmethyldimethoxysilane-tetraethoxysilane copolymer, 3-acryloyloxypropylmethyldiethoxysilane-tetramethoxysilane copolymer, 3-Acryloyloxypropylmethyldiethoxysilane-Tetraethoxysilane Copolymer acryloyloxypropyl group-containing copolymers such as vinyltrimethoxysilane-tetramethoxysilane copolymer, vinyltrimethoxysilane-tetraethoxysilane copolymer, vinyltriethoxysilane-tetramethoxysilane copolymer, vinyltriethoxysilane-tetraethoxysilane copolymer, vinylmethyldimethoxysilane-tetramethoxysilane copolymer, vinylmethyldimethoxysilane-tetraethoxysilane copolymer, vinylmethyldiethoxysilane-tetramethoxysilane copolymer, Vinylmethyldiethoxysilane-Tetraethoxysilane Copolymer Vinyl group-containing copolymers such as; 3-aminopropyltrimethoxysilane-tetramethoxysilane copolymer, 3-aminopropyltrimethoxysilane-tetraethoxysilane copolymer, 3-aminopropyltriethoxysilane-tetramethoxysilane copolymer, 3-aminopropyltriethoxysilane-tetraethoxysilane copolymer, 3-aminopropylmethyldimethoxysilane-tetramethoxysilane copolymer, 3-aminopropylmethyldimethoxysilane-tetraethoxysilane copolymer, 3-aminopropylmethyldiethoxysilane-tetramethoxysilane copolymer, 3-Aminopropylmethyldiethoxysilane-tetraethoxysilane copolymer and amino group-containing copolymers such as those mentioned above.

[0154] Most of the silane compounds exemplified above are liquid. The content of the silane compound in the adhesive composition is usually 0.01 parts by mass or more and 10 parts by mass or less, preferably 0.05 parts by mass or more and 5 parts by mass or less, more preferably 0.2 parts by mass or more and 0.4 parts by mass or less, relative to 100 parts by mass of the (meth)acrylic resin. When the content of the silane compound is 0.01 parts by mass or more, it is easy to obtain an effect of improving the adhesion between the adhesive layer 20 and an optical member such as a glass substrate. In addition, when the content of the silane compound is 10 parts by mass or less, it is possible to suppress the bleeding out of the silane compound from the adhesive layer.

[0155] [3-5] Other ingredients The adhesive composition may contain additives such as a crosslinking catalyst, a weathering stabilizer, a tackifier, a plasticizer, a softener, a dye, a pigment, an inorganic filler, light-scattering fine particles, a resin other than a (meth)acrylic resin, etc. In addition, an ultraviolet-curable compound may be blended into the adhesive composition, and after forming an adhesive layer, the adhesive layer may be cured by irradiating with ultraviolet light to form a harder adhesive layer. Examples of the crosslinking catalyst include amine compounds such as hexamethylenediamine, ethylenediamine, polyethyleneimine, hexamethylenetetramine, diethylenetriamine, triethylenetetramine, isophoronediamine, trimethylenediamine, polyamino resins, and melamine resins.

[0156] [3-6] Formation of adhesive layer The adhesive layer 20 can be obtained by dissolving or dispersing each component constituting the above-mentioned adhesive composition in a solvent to prepare a solvent-containing adhesive composition, which is then applied onto a substrate film or a polarizing plate 10 and dried.

[0157] The base film is generally a thermoplastic resin film, and a typical example thereof is a release-treated separate film, for example, a film made of a resin such as polyethylene terephthalate, polybutylene terephthalate, polycarbonate, polyarene, etc., on the surface on which the pressure-sensitive adhesive layer is formed, which is subjected to a release treatment such as silicone treatment, etc. For example, a pressure-sensitive adhesive composition is directly applied to the release-treated surface of a separate film to form a pressure-sensitive adhesive layer, and this pressure-sensitive adhesive layer with separate film is laminated on polarizing plate 10 to obtain a pressure-sensitive adhesive layer-attached polarizing plate. The pressure-sensitive adhesive composition may be directly applied to the surface of the polarizing plate 10 to form a pressure-sensitive adhesive layer, and if necessary, a separate film may be laminated on the outer surface of the pressure-sensitive adhesive layer to form a pressure-sensitive adhesive layer-attached polarizing plate. When providing the adhesive layer on the surface of polarizing plate 10, it is preferable to subject the bonding surface of polarizing plate 10 and / or the bonding surface of the adhesive layer to a surface activation treatment such as plasma treatment, corona treatment, etc., and it is more preferable to subject the layer to corona treatment. Alternatively, a pressure-sensitive adhesive composition may be applied onto a second separate film to form a pressure-sensitive adhesive layer, a pressure-sensitive adhesive sheet may be prepared by laminating a separate film onto the formed pressure-sensitive adhesive layer, and the second separate film may be peeled off from the pressure-sensitive adhesive sheet to laminate the pressure-sensitive adhesive layer with the separate film onto the polarizing plate 10. The second separate film used has weaker adhesion to the pressure-sensitive adhesive layer than the separate film and is easier to peel off.

[0158] The thickness of the pressure-sensitive adhesive layer 20 is preferably 5 μm or more and 45 μm or less, more preferably 10 μm or more and 30 μm or less, and even more preferably 5 μm or more and 25 μm or less. Having the thickness of the pressure-sensitive adhesive layer in this range can be advantageous in suppressing deterioration of adhesion over time.

[0159] <Image display device> 1 to 3, the image display device is a laminate of pressure-sensitive adhesive layer-attached polarizing plates 25, 26, and 27 and an image display element 30. Typically, an image display device includes the image display element 30, and the pressure-sensitive adhesive layer-attached polarizing plates 25, 26, and 27 laminated thereon with the pressure-sensitive adhesive layer 20 interposed therebetween. According to the pressure-sensitive adhesive layer-attached polarizing plates 25, 26, and 27 of the present invention, it is possible to provide an image display device in which deterioration of adhesion over time is suppressed.

[0160] Examples of the image display element 30 include image display elements such as a liquid crystal cell and an organic EL display element. Examples of a layer in contact with the pressure-sensitive adhesive layer 30 of the image display element 30 include a substrate. Examples of the substrate include a thermoplastic resin film and a glass substrate. EXAMPLES

[0161] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples. In the following, parts and % representing amounts used or contents are based on mass unless otherwise specified.

[0162] <Production Example 1: Preparation of adhesive layer> (1) Preparation of Pressure Sensitive Adhesive Composition (Meth)acrylic resin (Mw is 142×10 4 A pressure-sensitive adhesive composition containing a crosslinker (having a molecular weight distribution (Mw / Mn) of 4.8) and a silane compound was prepared. 6 parts by mass of an antistatic agent per 100 parts by mass of a (meth)acrylic resin was mixed with this pressure-sensitive adhesive composition, and ethyl acetate was added to the composition so that the solid content concentration was 28% by mass to prepare a solution of pressure-sensitive adhesive composition a. Furthermore, the pressure-sensitive adhesive composition was diluted with ethyl acetate without mixing the antistatic agent to prepare a solution of pressure-sensitive adhesive composition b so that the solid content concentration was 28% by mass.

[0163] The crosslinking agent was "Coronate L" available from Tosoh Corporation (ethyl acetate solution of trimethylolpropane adduct of tolylene diisocyanate: solids concentration 75% by mass). The silane compound was "KBM-403" (3-glycidoxypropyltrimethoxysilane) obtained from Shin-Etsu Chemical Co., Ltd. The antistatic agent is N-decylpyridinium bis(fluorosulfonyl)imide (molecular weight 545.5).

[0164] (2) Preparation of adhesive layer Each of the pressure-sensitive adhesive compositions a and b prepared in (1) above was applied to the release-treated surface of a second separate film made of a release-treated polyethylene terephthalate film ("PLR-382190" obtained from Lintec Corporation) using an applicator so that the thickness after drying would be 20 μm, and the applied film was dried at 100° C. for 1 minute to prepare pressure-sensitive adhesive layers a and b. Thereafter, a separate film was attached to the exposed surface of the pressure-sensitive adhesive layer to prepare pressure-sensitive adhesive sheets a and b.

[0165] (3) Preparation of Curable Resin Composition In terms of solid content, 3,4-epoxycyclohexylmethyl, an alicyclic epoxy compound, 35 parts by mass of 3,4-epoxycyclohexane carboxylate (product name: Celloxide 2021P, manufactured by Daicel Chemical Industries, Ltd.) and 2-[4-(2,3-epoxypropoxy)phenyl]-2-[4-[1,1-bis[4-([2,3-epoxypropoxy]phenyl]ethyl]phenyl]propane (product name: TECHMORE The respective components were mixed so as to prepare curable resin composition a, so as to obtain 15 parts by mass of VG3101L (product of Printec Co., Ltd.), 50 parts by mass of bis(3-ethyl-3-oxetanylmethyl)ether (product name: OXT-221, product of Toagosei Co., Ltd.) as an oxetane compound, 4.5 parts by mass of propylene carbonate of triarylsulfonium hexafluorophosphate (product name: CPI-100P, product of San-Apro Co., Ltd.) as a polymerization initiator, and 0.25 parts by mass of a silicone-based leveling agent (product name: SH710, product of Dow Corning Toray Co., Ltd.) as a leveling agent.

[0166] <Examples, Comparative Examples, and Reference Examples> Example 1 A polarizing plate with an adhesive layer having the same structure as the polarizing plate with an adhesive layer 25 shown in FIG. 1 was produced. A surface-treated triacetyl cellulose film (corresponding to the second protective film) was attached to one side of a polarizing plate with a thickness of 12 μm, in which iodine was adsorbed and oriented on a uniaxially stretched polyvinyl alcohol film, via a water-based adhesive, and a triacetyl cellulose film with a thickness of 20 μm (corresponding to the first protective film) was attached to the other side via a water-based adhesive, and the film was dried at 80° C. for 3 minutes to produce a polarizing plate. The surface-treated triacetyl cellulose film used above was a film (product name: 25KCHCN-TC (manufactured by Toppan Printing Co., Ltd.)) in which a surface-treated layer with a thickness of 7 μm (a hard coat layer using an acrylic resin) was formed on one side of a triacetyl cellulose film with a thickness of 25 μm, and the film was attached to the polarizing plate so that the surface opposite to the surface on which the surface-treated layer was formed was the polarizing side. Then, the surface of the adhesive layer a exposed by peeling off the second separate film of the adhesive sheet a prepared above was attached to the surface of the first protective film of the polarizing plate using a laminator, and the film was cured for 5 days under a condition of relative humidity of 65% to prepare a polarizing plate with an adhesive layer. The triacetyl cellulose film having a thickness of 20 μm, which corresponds to the first protective film, has a water absorption rate of 3.5% to 7.0% and a moisture permeability of 600 g / m 2 24h or more, volume resistance is 10 10 Ω cm~10 4 The value was Ω·cm.

[0167] Example 2 A polarizing plate with an adhesive layer having the same structure as the polarizing plate with an adhesive layer 26 shown in FIG. 2 was produced. A surface-treated triacetyl cellulose film (trade name: 25KCHCN-TC, corresponding to the second protective film) was attached to one side of a polarizer having a thickness of 7 μm, in which iodine was adsorbed and oriented on a uniaxially stretched polyvinyl alcohol film, via a water-based adhesive, and a curable resin composition a was applied to the other side and cured by irradiating with ultraviolet light to form a curable resin composition cured layer, thereby producing a polarizing plate. The surface of the adhesive layer a exposed by peeling off the second separate film of the adhesive sheet a produced above was attached to the surface of the curable resin composition cured layer of the polarizing plate, thereby producing the adhesive layer-attached polarizing plate of Example 2.

[0168] Comparative Example 1 A 32 μm-thick triacetyl cellulose film (corresponding to the second protective film) was attached to one side of a 12 μm-thick polarizer in which iodine was adsorbed and oriented on a uniaxially stretched polyvinyl alcohol film, via a water-based adhesive, and a 23 μm-thick cycloolefin polymer film (corresponding to the first protective film) was attached to the other side via a water-based adhesive to produce a polarizing plate. The surface of the adhesive layer a exposed by peeling off the second separate film of the adhesive sheet a produced above was attached to the surface of the first protective film of the polarizing plate, to produce a polarizing plate with an adhesive layer of Comparative Example 1. The 23 μm-thick cycloolefin polymer film corresponding to the first protective film had a water absorption rate of <0.01% and a moisture permeability of <0.01 g / m 2 24h, volume resistivity >10 16 The value was Ω·cm.

[0169] (Reference example 1) The surface of the adhesive layer b exposed by peeling off the second separate film of the adhesive sheet b prepared above was bonded to the surface of the first protective film of the polarizing plate of Comparative Example 1 to prepare the adhesive layer-attached polarizing plate of Reference Example 1.

[0170] <Measurement of the rate of change in resistance value ΔR> For the polarizing plates with adhesive layers of Examples 1 and 2 and Comparative Example 1, two samples (Samples 1 and 2) were cut out into rectangular shapes measuring 5 cm wide and 5 cm long. Each sample was left standing for 1 hour in an environment of 23°C and 55% RH with the separate film attached to the surface of the adhesive layer. Thereafter, the separate film on the surface of the adhesive layer was peeled off, and the electrode part of a high resistivity meter (Hiresta-UP, manufactured by Mitsubishi Chemical Corporation) was brought into contact with the surface of the adhesive layer of each sample, and the resistance value (referred to as "resistivity R1") was measured under the conditions of an applied voltage of 100 V and an application time of 30 seconds.

[0171] Next, each sample was attached to the surface of a glass plate (manufactured by Corning) wiped with ethanol so that the adhesive layer was in contact with the glass plate, and autoclaved (50°C, 0.5 MPa, 20 minutes). The autoclaved sample was left to stand in an oven at 85°C for 100 hours, and then left to stand in an environment of 23°C and 55% RH for 1 hour. Then, the electrode part of a high resistivity meter (Hiresta-UP, manufactured by Mitsubishi Chemical Corporation) was brought into contact with the surface of the adhesive layer of each sample, and the resistance value (referred to as "resistivity R2") was measured under the conditions of an applied voltage of 100V and an application time of 30 seconds.

[0172] The rate of change ΔR (%) in the resistance value of the surface of the pressure-sensitive adhesive layer opposite to the polarizing plate side before and after being held at a temperature of 85° C. for 100 hours was calculated using the following formula (3). ΔR = [(R2-R1) / R1] × 100 (3)

[0173] For the pressure-sensitive adhesive layer-attached polarizing plates of Examples 1 and 2 and Comparative Example 1, the average value of R1 of the two samples was taken as R1, and the average value of R2 of the two samples was taken as R2, and ΔR was calculated using these values ​​according to formula (3). This ΔR was taken as ΔR for Examples 1 and 2 and Comparative Example 1. The results are shown in Table 1.

[0174] [Table 1]

[0175] <Peel force measurement> For the polarizing plates with adhesive layer of Examples 1 and 2 and Comparative Example 1, samples were cut into strips with a length of 10 cm and a width of 25 mm, with the stretching direction of the polarizer being the vertical direction. Each sample was attached to the surface of a glass plate (manufactured by Corning) wiped with ethanol so that the adhesive layer was in contact with the glass plate, and autoclaved (50°C, 0.5 MPa, 20 minutes). The autoclaved sample was left to stand in an oven at 85°C for 100 hours, and then the sample was taken out and set in a tensile tester (AUTOGRAPH AG-X plus, manufactured by Shimadzu Corporation) in a thermostatic chamber set at 85°C. Then, in an environment of 85°C, the sample was peeled in the vertical direction at a peel angle of 180° and a peel speed of 300 mm / min to measure the peel strength. The peel strength was taken as the average value of the section in which the peel value was stable. The results are shown in Table 2.

[0176] <Drop durability test> For the adhesive layer-attached polarizing plates of Examples 1 and 2, Comparative Example 1, and Reference Example 1, a rectangular sample (140 mm long, 70 mm wide) with four right-angled corners (hereinafter referred to as "right-angled rectangular") and a rectangular sample (140 mm long, 70 mm wide) with four rounded corners with a curvature radius of 1.0 mm (hereinafter referred to as "rounded rectangular") were cut out. FIG. 6 shows the outline of the right-angled rectangular sample. For each sample, the second separate film on the surface of the adhesive layer was peeled off, and the adhesive layer was laminated on the surface of a glass plate (thickness 0.5 mm) and bonded by pressing with a load of 50 N for 10 seconds to obtain an evaluation sample. The glass plate used here was prepared to have an outline 1 mm larger than the outline of the sample, and was bonded so that the distance between the outline of the glass plate and the outline of the sample was 1 mm. That is, for the right-angled rectangular sample, a glass plate (thickness 0.5 mm) measuring 142 mm in length and 72 mm in width with all four corners at right angles was prepared, and a right-angled rectangular polarizing plate with an adhesive layer was attached to this to prepare an evaluation sample. For the rounded rectangular sample, a rectangular glass plate (thickness 0.5 mm) measuring 142 mm in length and 72 mm in width with all four corners rounded with a curvature radius of 2.0 mm was prepared, and a rounded rectangular polarizing plate with an adhesive layer was attached to this to prepare an evaluation sample. Each evaluation sample was left standing in an oven at 85° C. for 100 hours, and then left standing in an environment at 23° C. and 55% RH for 1 hour. Then, a 160g weight was attached to the rear surface (the surface opposite to the surface bonded to the glass plate) of the polarizing plate of the evaluation sample. A drop test was performed on the evaluation sample with the weight attached, in which the evaluation sample was allowed to freely drop 60 times from a height of 1.2 m onto a concrete plate at room temperature (about 23°C). At this time, the direction of the drop was adjusted so that the six surfaces of the evaluation sample (the two main surfaces at the top and bottom, the two vertical side surfaces, and the two horizontal side surfaces, total of six surfaces) were downward in sequence. In other words, 10 cycles of a drop pattern were performed once for each of the six surfaces. After each drop, the polarizing plate and the glass plate were visually inspected to see if they were still bonded to each other, and the polarizing plate and the glass plate were evaluated as to whether peeling (separation) was observed between them during the 60 free drops. The results are shown in Table 2. A: No peeling was observed. B: Peeling was observed.

[0177] [Table 2] [Explanation of symbols]

[0178] 1 polarizer, 2 surface treatment layer, 3 second protective film, 4 first protective film, 10 polarizing plate, 20 pressure-sensitive adhesive layer, 25, 26, 27 pressure-sensitive adhesive layer-attached polarizing plates, 30 image display element.

Claims

1. A method for producing a pressure-sensitive adhesive layer-attached polarizing plate, comprising: a polarizing plate; and a pressure-sensitive adhesive layer laminated in contact with the polarizing plate, the method comprising the steps of: forming the pressure-sensitive adhesive layer from a pressure-sensitive adhesive composition; a step of bonding the pressure-sensitive adhesive layer to the polarizing plate to obtain the pressure-sensitive adhesive layer-attached polarizing plate; a standing step of standing the pressure-sensitive adhesive layer-attached polarizing plate to reduce an amount of the antistatic agent exposed on the surface of the pressure-sensitive adhesive layer, The pressure-sensitive adhesive layer-attached polarizing plate has four sides and four corners, At least one of the four corners is a round corner having a radius of curvature of 1.0 mm or more; The pressure-sensitive adhesive layer has a peel strength of 9.1 (N / 25 mm) or more, The pressure-sensitive adhesive composition contains a (meth)acrylic resin and an antistatic agent, The antistatic agent is an ionic compound, the pressure-sensitive adhesive composition contains 0.1 parts by mass or more and 10 parts by mass or less of the ionic compound relative to 100 parts by mass of the (meth)acrylic resin, The standing process is a process of standing the adhesive layer-attached polarizing plate at a temperature of 85°C for 100 hours, and is performed so that the rate of change ΔR [%] calculated by equation (3) satisfies the relationship of equation (1), where the resistance values ​​of the surface of the adhesive layer opposite the polarizing plate side before and after the standing process are R1 [Ω / □] and R2 [Ω / □], respectively. ΔR=[(R2-R1) / R1]×100 (3) ΔR≧25 (1)

2. The method of claim 1 , wherein the outer shape is rectangular.

3. The polarizing plate includes a polarizer layer and a first protective film, the first protective film is a polar resin film, The method according to claim 1 , wherein the first protective film and the pressure-sensitive adhesive layer are in contact with each other.

4. The polarizing plate includes a polarizer layer and a cured layer of a curable resin composition, The method according to claim 1 , wherein the cured layer of the curable resin composition and the pressure-sensitive adhesive layer are in contact with each other.

Citation Information

Patent Citations

  • Acrylate-based pressure-sensitive adhesive, and polarizing plate and liquid crystal display device obtained using the same

    JP2008144125A

  • Pressure-sensitive adhesive for optical member and optical member

    JP2009132909A

  • Polarizing plate, optical member, and liquid crystal display

    JP2010039298A

  • Optical film with adhesive and optical laminate using it

    JP2010066755A

  • Optical film with adhesive and optical laminate using the same

    JP2010066756A